[18]Annulene put into a new perspective. - Lungerich, Dominik; Nizovtsev, Alexey; Heinemann, Frank Wilhelm; Hampel, Frank; Meyer, Karsten; Majetich, George; Schleyer, Paul V. R.; Jux, Norbert (Chemical Communications, 2016)
New insights into [18]annulene were gained by looking more closely at its X-ray structure, revealing a close face-to-face stacking of 3.16 Å in a herringbone-like crystal packing. Hexadehydro[18]annulene was co-crystalized in a benzene matrix, demonstrating the stabilizing role of intercalated solvent molecules in solid annulenes.

2H-Tetrakis(3,5-di-tert-butyl)phenylporphyrin on a Cu(110) Surface: Room-Temperature Self-Metalation and Surface-Reconstruction-Facilitated Self-Assembly - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Schuster, Ralf; Lungerich, Dominik; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Chemistry - A European Journal, 2016)
The adsorption behavior of 2H-tetrakis(3,5-di-tert-butyl)phenylporphyrin (2HTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces have been investigated by using variable-temperature scanning tunneling microscopy (STM) under ultrahigh vacuum conditions. On the bare Cu(110) surface, individual 2HTTBPP molecules are observed. These molecules are immobilized on the surface with a particular orientation with respect to the crystallographic directions of the Cu(110) surface and do not form supramolecular aggregates up to full monolayer coverage. In contrast, a chiral supramolecular structure is formed on the Cu(110)-(2x1)O surface, which is stabilized by van der Waals interactions between the tert-butyl groups of neighboring molecules. These findings are explained by weakened molecule-substrate interactions on the Cu(110)-(2x1)O surface relative to the bare Cu(110) surface. By comparison with the corresponding results of Cu-tetrakis(3,5-di-tert-butyl)phenylporphyrin (CuTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces, we find that the 2HTTBPP molecules can self-metalate on both surfaces with copper atoms from the substrate at room temperature (RT). The possible origins of the self-metalation reaction at RT are discussed. Finally, peculiar irreversible temperature-dependent switching of the intramolecular conformations of the investigated molecules on the Cu(110) surface was observed and interpreted.
Keywords: adsorption; porphyrinoids; scanning tunneling microscopy; self-assembly; surfaces and interfaces

500-Fold Amplification of Small Molecule Circularly Polarised Luminescence through Circularly Polarised FRET - Wade, Jessica; Brandt, Jochen R.; Reger, David; Zinna, Francesco; Amsharov, Konstantin; Jux, Norbert; Andrews, David L.; Fuchter, Matthew J. (Angewandte Chemie International Edition, 2020)
Strongly dissymmetric circularly polarised (CP) luminescence from small organic molecules could transform a range of technologies, such as display devices. However, highly dissymmetric emission is usually not possible with small organic molecules, which typically give dissymmetric factors of photoluminescence (gPL) less than 10−2. Here we describe an almost 103-fold chiroptical amplification of a π-extended superhelicene when embedded in an achiral conjugated polymer matrix. This combination increases the |gPL| of the superhelicene from approximately 3×10−4 in solution to 0.15 in a blend film in the solid-state. We propose that the amplification arises not simply through a chiral environment effect, but instead due to electrodynamic coupling between the electric and magnetic transition dipoles of the polymer donor and superhelicene acceptor, and subsequent CP Förster resonance energy transfer. We show that this amplification effect holds across several achiral polymer hosts and thus represents a simple and versatile approach to enhance the g-factors of small organic molecules.
CRIS-Team Scopus Importer:2020-12-18
Keywords: chirality; circular dichroism; FRET; helical structures; polymers

A comparative mechanistic study of the reversible binding of NO to a water-soluble octa-cationic FeIII porphyrin complex - Jee, Joo-Eun; Wolak, Maria; Balbinot, Domenico; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2006)
The water-soluble, non-μ-oxo dimer-forming porphyrin, [5,10,15,20-tetrakis-4′-t-butylphenyl-2′,6′-bis-(N-methylene- (4″-t-butylpyridinium))porphyrinato]iron(III) octabromide, (P )Fe, with eight positively charged substituents in the ortho positions of the phenyl rings, was characterized by UV-vis and H NMR spectroscopy and O NMR water-exchange studies in aqueous solution. Spectrophotometric titrations of (P)Fe indicated a pK value of 5.0 for coordinated water in (P)Fe(HO). The monohydroxo-ligated (P)Fe(OH)(HO) formed at 5 < pH < 12 has a weakly bound water molecule that undergoes an exchange reaction, k = 2.4 × 10 s, significantly faster than water exchange on (P)Fe (HO), viz. k = 5.5 × 10 s at 25°C. The porphyrin complex reacts with nitric oxide to yield the nitrosyl adduct, (P)Fe (NO)(L) (L = HO or OH). The diaqua-ligated (P)Fe(HO) binds and releases NO according to a dissociatively activated mechanism, analogous to that reported earlier for other (P)Fe(H O) complexes. Coordination of NO to (P )Fe(OH)(HO) at high pH follows an associative mode, as evidenced by negative ΔS and ΔV values measured for this reaction. The observed ca. 10-fold decrease in the NO binding rate on going from six-coordinate (P)Fe(HO) (k = 15.1 × 10 M s) to (P)Fe(OH)(HO) (k = 1.56 × 10 M s at 25°C) is ascribed to the different nature of the rate-limiting step for NO binding at low and high pH, respectively. The results are compared with data reported for other water-soluble iron(III) porphyrins with positively and negatively charged meso substituents. Influence of the porphyrin periphery on the dynamics of reversible NO binding to these (P)Fe complexes as a function of pH is discussed on the basis of available experimental data. © 2006 American Chemical Society.

A Comprehensive Study on Tetraaryltetrabenzoporphyrins - Ruppel, Michael; Lungerich, Dominik; Sturm, Sabrina; Lippert, Rainer; Hampel, Frank; Jux, Norbert (Chemistry - A European Journal, 2020)
Tetraaryltetrabenzoporphyrins (TATBPs) show, due to their optoelectronic properties, rising potential as dyes in various fields of physical and biomedical sciences. However, unlike in the case of porphyrins, the potential structural diversity of TATBPs has been explored only to little extent, owed mainly to synthetic hurdles. Herein, we prepared a comprehensive library of 30 TATBPs and investigated their fundamental properties. We elucidated structural properties by X-ray crystallography and found explanations for physical properties such as solubility. Fundamental electronic aspects were studied by optical spectroscopy as well as by electrochemistry and brought in context to the stability of the molecules. Finally, we were able to develop a universal synthetic protocol, utilizing a readily established isoindole synthon, which gives TATBPs in high yields, regardless of the nature of the used arylaldehyde and without meticulous chromatographic purifications steps. This work serves as point of orientation for scientists, that aim to utilize these molecules in materials, nanotechnological, and biomedical applications.
CRIS-Team WoS Importer:2020-02-18

Acylation of Hexaphenylbenzene for the Synthesis of [5]Cumulenes - Johnson, Matthew A.; Martin, Max; Cocq, Kévin; Jux, Norbert; Ferguson, Michael J.; Tykwinski, Rik R. (European Journal of Organic Chemistry, 2022)
The Friedel-Crafts acylation of hexaphenylbenzene is reported, and the reaction favorably provides the monoacylated products 1 a and 1 b. The resulting ketones 1 a and 1 b are used as precursors for the formation of [5]cumulenes, including 6 b in which the sterically demanding HPB moiety affords a diethynyl[5]cumulene that features significant stability (persistence) versus the analog 6 c which lacks the HPB endgroups. The unsymmetrical substitution pattern of the two most soluble derivatives 6 b and 6 c, allows for estimation of rotational barriers for diethynyl[5]cumulenes via VT NMR studies of cis-trans isomerization. For both molecules, the barrier to rotation is ca. 15 kcal mol−1, which is attenuated in comparison to other [5]cumulenes due to the presence of the ethynyl endgroups.
CRIS-Team Scopus Importer:2022-02-11

Addressing Environmental Challenges of Porphyrin Mixtures Obtained from Statistical Syntheses - Hölzel, Helen; Muth, Maximilian; Lungerich, Dominik; Jux, Norbert (Chemistry Methods, 2021)
Syntheses of complex molecular mixtures on the preparative scale are often challenging steps for chemists, which go hand in hand with expensive purification steps. Herein, the preparation and isolation of unsymmetrically substituted porphyrins, obtained from statistical reactions between two benzaldehydes, were investigated. Therefore, a semi-automated modular process was developed to lower the consumable costs, save time, and reduce waste production. We utilized a monomode microwave reactor equipped with an autosampler, and a medium pressure liquid chromatography (MPLC) flash purification device, equipped with a UV/Vis detector and a re-usable glass column packed with SiO2. With this method, it was possible to synthesize and purify several statistical porphyrin mixtures, while simultaneously reducing the environmental factor (E-factor) significantly, compared to conventionally performed porphyrin syntheses. Our approach shows that a sustainable investigation of academically relevant low-symmetrical porphyrins can be carried out feasibly, without sacrificing invested time.
CRIS-Team Scopus Importer:2024-12-16
Keywords: chromatography; E-factor; Porphyrin; statistical synthesis; sustainability

Adsorption and self-assembly of a mono-cyano Zn-tetraphenylporphyrin derivative on KBr(001) and MgO(001) - Ammon, Maximilian Michael; Devarajulu, Mirunalini; LIU, YI; Gurrath, Martin; Lungerich, Dominik; Jux, Norbert; Meyer, Bernd; Maier, Sabine (Surface Science, 2022)
The adsorption and self-assembly of a Zn-tetraphenylporphyrin derivative (Zn-pCNTPP) with a cyano group was investigated on KBr(001) and MgO(001) using low-temperature non-contact atomic force microscopy (nc-AFM) combined with dispersion-corrected density-functional theory (DFT). The deposition of Zn-pCNTPP at submonolayer coverage leads on both surfaces to self-assembled networks, in which the porphyrin assumes a planar adsorption configuration with the macrocycle parallel to the surface. DFT calculations confirm the planar adsorption geometry and reveal important differences in the adsorption on KBr vs. MgO. While a global minimum structure is found on KBr due to a strong CN⋯K interaction, multiple and energetically nearly equivalent adsorption sites occur on MgO. Therefore, commensurate adsorption on KBr is suggested, while optimizing the molecule–molecule over molecule–surface interactions is more important on MgO, which is experimentally both evidenced by the nc-AFM data. The expected Zn adsorption site ontop of the anion is the energetically most favored configuration only on KBr, while on MgO, it is above the surface cation.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Adsorption geometry; Dispersion-corrected density-functional theory; Molecular self-assembly; Non-contact atomic force microscopy; Porphyrins

Adsorption Behavior of a Cyano-Functionalized Porphyrin on Cu(111) and Ag(111): From Molecular Wires to Ordered Supramolecular Two-Dimensional Aggregates - Lepper, Michael; Schmitt, Tobias; Gurrath, Martin; Raschmann, Marco; Zhang, Liang; Stark, Michael Werner; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Schneider, M. Alexander; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2017)
We investigate the impact of peripheral cyano functionalization of the previously well-studied 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy (STM) and density functional theory (DFT). The adsorption behavior of 2H-tetralds(p-cyano)-phenylporphyrin (2HTCNPP) is studied at room temperature and at 80 K on Cu(111) and Ag(111). Interestingly, the cyano-functionalized porphyrins tend to form isolated ID chains on Cu(111), in particular after mild annealing at 350 K. The individual 2HTCNPPs as well as the formed chains are oriented along the main crystallographic directions of the Cu(111) substrate due to a strongly attractive and site-specific interaction between the iminic nitrogens of the 2HTCNPP and Cu substrate atoms. The linking within the 1D molecular chains is realized by Cu adatoms as evidenced by comparison of STM and DFT. In contrast, on Ag(111) the molecules assemble into 2D supramolecular layers with long-range order and a square unit cell, stabilized by molecule-molecule interactions. The orientation of the molecules with respect to the unit cell lattice vectors leads to organizational chirality. By codeposition of cobalt, the porphyrin molecules are metalated at room temperature. We did not observe any evidence for metal-organic network formation on Ag(111), even after varying the deposition parameters or the order of metal and porphyrin deposition. Our study shows that cyano functionalization of porphyrins can give rise to novel and unique self-assembled structures like 1D molecular chains without any cross-connections via adatom linking.

A facile route to water-soluble coronenes and benzo[ghi]perylenes - Schmidt, Cordula; Lang, Nina; Jux, Norbert; Hirsch, Andreas (Chemistry - A European Journal, 2011)
Click reactions at the bay-position of perylenes and a new route to benzo[ghi]perylenes and coronenes are presented. Irradiation with light leads to an electrocyclic reaction of the newly formed triazole ring(s) with the neighbouring bay-positions of the perylene core and after oxidation by air, the benzo[ghi]perylenes and coronenes are obtained. By using Newkome dendrimers as substituents for perylene diimides (PDIs), water solubility can be achieved after removal of the tert-butyl protecting groups. The aggregation and optical properties of the bay-functionalised PDIs, benzo[ghi]perylenes and coronenes are investigated by absorption and fluorescence spectroscopy. Given the green light: Click reactions at the bay-positions of perylene diimides were carried out for the first time. The newly formed triazole units undergo electrocyclisation reactions with the neighbouring perylene bay-position to form benzoperylenes or coronenes (see scheme). The reactions occur in solution in 55-87%yield by irradiation with light, providing a simple, new and environmentally friendly route to coronenes and benzoperylenes. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar pi Systems - Reger, David; Haines, Philipp; Amsharov, Konstantin; Schmidt, Julia A.; Ullrich, Tobias; Bönisch, Simon; Hampel, Frank; Görling, Andreas; Nelson, Jenny; Jelfs, Kim E.; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2021)
We designed a straightforward synthetic route towards a full-fledged family of pi-extended helicenes: superhelicenes. They have two hexa-peri-hexabenzocoronenes (HBCs) in common that are connected via a central five-membered ring. By means of structurally altering this 5-membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. In-depth physico-chemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was rounded-off by crystal structure analyses. Mixed stacks of M- and P-isomers led to twisted molecular wires. Using such stacks, charge-carrier mobilities were calculated, giving reason to expect outstanding hole transporting properties.
CRIS-Team WoS Importer:2021-07-23

A Functional Hexaphenylbenzene Library Comprising of One, Three, and Six Peripheral Rylene-Diimide Substituents - Dusold, Carolin; Platzer, Benedikt; Haines, Philipp; Reger, David; Jux, Norbert; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Synthesis and characterization of a series of rylene-diimide substituted hexaphenylbenzenes (HPBs) is presented. The direct connection of the rylene-diimide units to the HPBs via the imide-N-position without any linkers as well as the use of naphthalene-diimides (NDIs) next to perylene-diimides (PDIs) is unprecedented. While mono-substituted products were obtained by imidization reactions with amino-HPB and the respective rylene-monoimides, key step for the formation of tri- and hexa-substituted HPBs is the Co-catalysed cyclotrimerization. Particular emphasis for physic-chemical characterization was on to the number of NDIs/PDIs per HPB and the overall substitution patterns. Lastly, Scholl oxidation conditions were applied to all HPB systems to generate the corresponding hexa-peri-hexabenzocoronenes (HBCs). Importantly, the efficiency of the transformation strongly depends on the number of NDIs/PDIs. While three rylene-diimide units already hinder the Scholl reaction, the successful synthesis of mono-substituted HBCs is possible.
CRIS-Team WoS Importer:2021-01-15

A Hexabenzocoronene-Based Helical Nanographene - Martin, Max; Hampel, Frank; Jux, Norbert (Chemistry - A European Journal, 2020)
A synthetic route towards a novel hexabenzocoronene-based helical nanographene motif was developed. A hexaphenylbenzene precursor was therefore designed, which cannot undergo, due to steric restrictions, a complete planarization reaction. This precursor was transformed under oxidative cyclodehydrogenation conditions to a π-extended [5]helicene, which was fully characterized including X-ray diffraction analysis.
CRIS-Team Scopus Importer:2020-07-24
Keywords: carbon allotrope; helicene; hexabenzocoronene; nanographene; polycyclic aromatic hydrocarbons

A Singular Molecule-to-Molecule Transformation on Video: The Bottom-Up Synthesis of Fullerene C60from Truxene Derivative C60H30 - Lungerich, Dominik; Hoelzel, Helen; Harano, Koji; Jux, Norbert; Amsharov, Konstantin; Nakamura, Eiichi (ACS nano, 2021)
Singular reaction events of small molecules and their dynamics remain a hardly understood territory in chemical sciences since spectroscopy relies on ensemble-averaged data, and microscopic scanning probe techniques show snapshots of frozen scenes. Herein, we report on continuous high-resolution transmission electron microscopic video imaging of the electron-beam-induced bottom-up synthesis of fullerene C60 through cyclodehydrogenation of tailor-made truxene derivative 1 (C60H30), which was deposited on graphene as substrate. During the reaction, C60H30 transformed in a multistep process to fullerene C60. Hereby, the precursor, metastable intermediates, and the product were identified by correlations with electron dose-corrected molecular simulations and single-molecule statistical analysis, which were substantiated with extensive density functional theory calculations. Our observations revealed that the initial cyclodehydrogenation pathway leads to thermodynamically favored intermediates through seemingly classical organic reaction mechanisms. However, dynamic interactions of the intermediates with the substrate render graphene as a non-innocent participant in the dehydrogenation process, which leads to a deviation from the classical reaction pathway. Our precise visual comprehension of the dynamic transformation implies that the outcome of electron-beam-initiated reactions can be controlled with careful molecular precursor design, which is important for the development and design of materials by electron beam lithography.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cyclodehydrogenation; DFT-modeling; fullerene; polycyclic aromatic hydrocarbon; single-molecule dynamics; transmission electron microscopy

Asymmetrically Fused Nanographene-Porphyrin Architectures - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (European Journal of Organic Chemistry, 2025)
A strategy to combine three standalone aromatic building blocks in one coherent, fully conjugated molecule is presented. Namely, benzene, pyrene, and hexa-peri-hexabenzocoronene (HBC) are assembled around a central porphyrin core in an ABAC type of geometry and interconnected under oxidative Scholl conditions to achieve merging of the individual π-systems. The three asymmetric porphyrin conjugates obtained this way exhibit intriguing absorption features, namely strongly red-shifted and broadened spectra. The presented series of molecules demonstrates the ability to control and influence these optical properties with high precision by altering the size of the aromatic system in a controlled manner. Density functional theory calculations gave more profound insights into the electronic structure and optical transitions of the investigated fused architectures.
CRIS-Team Scopus Importer:2025-01-31
Keywords: fusion reaction; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

A synthetic methodology toward π-extended porphyrin-rylenediimide conjugates - Oleszak, Christoph; Ritterhoff, Christian; Schulze, Erik; Hirsch, Andreas; Meyer, Bernd; Jux, Norbert (RSC Advances, 2025)
In this work, we present a straightforward synthetic route for the preparation of functionalized β-meso-fused porphyrins, which are subsequently connected to rylendiimides. The resulting donor-acceptor-type conjugates exhibit intriguing optical properties, such as panchromatism and profoundly bathochromically shifted absorption curves. A better understanding of the molecules' electronic structure was gained through density-functional theory calculations, which unveiled small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-01-31

Axial coordination of pyridyl-containing pentacenes to porphyrins - Waterloo, Andreas; Lippert, Rainer; Jux, Norbert; Tykwinski, Rik (Journal of Coordination Chemistry, 2015)
A pair of pentacenes that are functionalized in the 6-position with either a 3- or 4-pyridyl group via a triazole linker have been used to form complexes with a tetra(aryl)ruthenium(II) porphyrin through axial coordination. The pentacene–porphyrin dyads 5 and 6 have been structurally characterized through a combination of spectroscopic techniques. UV–vis spectroscopy shows that the absorption profiles of the two chromophores, the porphyrin and the pentacene, are complementary, providing absorptions throughout the UV and visible regions. While the dyads are reasonably stable in the solid state under ambient conditions they are, unfortunately, only stable in solution for hours when exposed to light and air.
EAM Import::2019-03-13

Benzohydroxamic acid on rutile TiO2(110)-(1×1)– a comparison of ultrahigh-vacuum evaporation with deposition from solution - Köbl, Julia; Fernández, Cynthia C.; Augustin, Lisa-Marie; Kataev, Elmar; Franchi, Stefano; Tsud, Nataliya; Pistonesi, Carolina; Pronsato, M. Estela; Jux, Norbert; Lytken, Ole; Williams, Federico J.; Steinrück, Hans-Peter (Surface Science, 2022)
Hydroxamic acids are an interesting anchor group for organic molecules on oxide surfaces, but very few studies exist on their adsorption on well-defined single-crystal surfaces under well-defined conditions. In the present paper, we use X-ray photoelectron spectroscopy to follow the adsorption of benzohydroxamic acid on a rutile TiO2(110)-(1×1) single-crystal surface. We compare evaporation in ultrahigh vacuum with deposition from ethanol and acetonitrile solutions. Furthermore, we carried out density functional theory calculations to support the assignment of adsorbates. Several species appear on the surface, which are most evident in the N 1s region. The low-coverage species can be explained as originating from a hydroxamate, and decomposed species related to oxygen vacancies or defects. Identification of the high-coverage species, however, remains elusive, and several possibilities are discussed.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Benzohydroxamic acid; Density functional theory calculations; TiO; X-ray photoelectron spectroscopy (XPS)

Benzoporphyrins: Selective Co-sensitization in Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Chemistry - A European Journal, 2016)
A novel class of dyes, namely benzoporphyrins, was synthesized and implemented into dye-sensitized solar cells. They feature complementary absorptions compared to N719, which renders them promising candidates for co-sensitization in DSSCs. Notably, metallated benzoporphyrins reveal a TiO2-nanoparticle attachment that is size and aggregation dependent. Therefore, unproductive energy-transfer events between the selectively attached dyes can be prevented. In light of the latter, an efficiency improvement of 39 % has been achieved upon selective adsorption of benzoporphyrins and N719 onto different layers of TiO2 photoelectrode.
EAM Import::2019-03-13

Building from Ga-Porphyrins: Synthesis of Ga-Acetylide Complexes Using Acetylenes and Polyynes - Walter, Vroni; Gao, Yueze; Grzegorzek, Norbert; Krempe, Maximilian; Hampel, Frank; Jux, Norbert; Tykwinski, Rik (Angewandte Chemie International Edition, 2019)
Multidimensional, conjugated building blocks have been formed through the axial coordination of polyynes to the central Ga atom of tetraarylporphyrins. Electron deficient pentafluorophenyl substituents in the meso-positions provide more stable σ-acetylide complexes to Ga than analogous structures with tert-butylphenyl groups. Mono-, di-, and triynes have been used, including a pyridyl endcapped diyne that allows for formation of porphyrin triads through coordination of the pyridyl ligand to a Ru porphyrin.
CRIS-Team Scopus Importer:2019-07-23
Keywords: axial σ-acetylide; Ga-porphyrin; hierarchical assembly; polyyne; supramolecular assembly

Catching metallic nitride endohedral fullerenes in organic and aqueous media - Strauß, Volker; Radhakrishnan, Shankara Gayathri; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2016)
Two bis-tetraphenylporphyrin tweezers-like conjugates bearing different linkers have been characterized by means of electrochemical and photophysical methods. The thrust of this work was the complexation of these bis-porphyrins with C60 and metallic nitride endohedral fullerenes (MNEF) like Sc3N@C80 in organic and in aqueus media - studied by a combination of steady-state and time-resolved spectroscopies. In the context of charge separation evidence for the formation of the 1a(•+)-Sc3N@C80 (•-) and 1c(•+)-Sc3N@C80(•-) charge separated states in organic and aqueous media, respectively, came from transient absorption spectroscopy. Multi-wavelength analyses afforded charge separated state lifetimes of around 400 ps.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charge-transfer; metallic nitride endohedral fullerenes; porphyrin; time-resolved spectroscopy; tweezers

Conformation Controls Mobility: 2H-Tetranaphthylporphyrins on Cu(111) - Kuliga, Jan; Massicot, Stephen; Adhikari, Rajan; Ruppel, Michael; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2020)
The adsorption behavior and the mobility of 2H-Tetranaphthylporphyrin (2HTNP) on Cu(111) was investigated by scanning tunneling microscopy (STM) at room temperature (RT). The molecules adsorb, like the structurally related 2HTPP, in the "inverted" structure with the naphthyl plane restricted to an orientation parallel to the Cu surface. The orientation of the four naphthyl groups yields altogether 16 possible conformations. Due to the existence of rotamer pairs, 10 different appearances are expected on the surface, and all of them are identified by STM at RT. Most interestingly, the orientation of the naphthyl groups significantly influences the diffusion behavior of the molecules on Cu(111). We identify three different groups of conformers, which are either immobile, medium or fast diffusing at RT. The mobility seems to decrease with increasing size of the footprint of the conformers on the surface.
CRIS-Team WoS Importer:2020-03-03

Controlling the Self-Metalation Rate of Tetraphenylporphyrins on Cu(111) via Cyano Functionalization - Lepper, Michael; Köbl, Julia; Zhang, Liang; Meusel, Manuel; Hölzel, Helen; Lungerich, Dominik; Jux, Norbert; De Siervo, Abner; Meyer, Bernd; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2018)
The reaction rate of the self-metalation of free-base tetraphenylporphyrins (TPPs) on Cu(111) increases with the number of cyano groups (n=0, 1, 2, 4) attached at the para positions of the phenyl rings. The findings are based on isothermal scanning tunneling microscopy (STM) measurements. At room temperature, all investigated free-base TPP derivatives adsorb as individual molecules and are aligned with respect to densely packed Cu substrate rows. Annealing at 400K leads to the formation of linear dimers and/or multimers via CN-Cu-CN bonds, accompanied by self-metalation of the free-base porphyrins following a first-order rate equation. When comparing the non-cyano-functionalized and the tetracyano-functionalized molecules, we find a decrease of the reaction rate by a factor of more than 20, corresponding to an increase of the activation energy from 1.48 to 1.59eV. Density functional theory (DFT) calculations give insights into the influence of the peripheral electron-withdrawing cyano groups and explain the experimentally observed effects.
Keywords: cyano functionalization; porphyrinoids; scanning tunneling microscopy; self-metalation; surface chemistry

Coverage- and temperature-induced self-metalation of tetraphenyltransdibenzoporphyrin on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto Dos Santos, Alisson; Jaekel, Simon; Adhikari, Rajan; Gazetas, Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Lytken, Ole; et al. (Journal of Physics: Condensed Matter, 2025)
We have investigated the adsorption and self-metalation of free-base tetraphenyltransdibenzoporphyrin (2H-TPtdBP) on Cu(111) as a function of coverage and temperature using scanning tunneling microscopy, x-ray photoelectron spectroscopy, temperature programmed desorption, and density-functional theory calculations. At low coverages (<0.16 molecules nm-2), we observe isolated individual molecules with an inverted conformation and no self-metalation up to 363 K. At higher coverages, both the formation of ordered islands and self-metalation are observed over time already at room temperature, and accelerate upon heating to 363 K. At 423 K, complete self-metalation occurs for all coverages up to the completed first layer. By comparing our results for 2H-TPtdBP to the existing literature on other tetraphenyl-based porphyrins, we demonstrate how adsorption and self-metalation can be tailored by the choice of substituents.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DFT; porphyrins; self-assembly; self-metalation; STM; TPD; XPS

Crystal Engineering of Sterically Shielded Hexa-peri-hexabenzocoronenes - Reger, David; Hampel, Frank; Jux, Norbert (Australian Journal of Chemistry, 2021)
The crystal structures of four pentakis-tert-butyl hexa-peri-hexabenzocoronenes (HBCs), each with an additional sixth substituent namely iodide, methoxy, formyl, and nitro, are presented. We show that the additional substituent has a significant impact on the packing in the solid state and the data obtained can be utilised for crystal engineering. By introducing an electron accepting substituent it was possible to achieve columnar arrangements that were previously unknown for such highly tert-butylated HBCs. In this way we provide insight into the aggregation behaviour of nanographenes with sterically highly shielded edges.
CRIS-Team WoS Importer:2021-05-14

Dissipation of electronic excitation energy within a C60 [6:0]-hexaadduct carrying 12 pyropheophorbide a moieties - Helmreich, Matthias; Ermilov, Eugeny; Meyer, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Journal of the American Chemical Society, 2005)
The synthesis and photophysical studies of a fullerene [6:0]-hexaadduct that carries 12 pyropheophorbide a units are reported. The synthesis started with the malonate 1, which was coupled under template conditions to C to give the hexaadduct 2. After removal of the protecting group with acid the dodecakis amino-substituted precursor compound 3 was generated. 3 was not isolated but directly reacted with the N-succinimid ester 4 of pyropheophorbide a (5), which delivered the desired fullerene [6:0]-hexaadduct 6 in excellent yield. The photophysical properties of 6 were studied and compared with those of the fullerene [5:1]-hexaadduct 7 with six pyropheophorbide a groups and the bispyropheophorbide a-fullerene [5:1]-hexaadduct 8. The pyropheophorbide a units in 6 undergo after light absorption very efficient energy transfer as well as partly excitonic interaction. The last process results in formation of energy traps, which could be resolved experimentally. Compared to the reference compounds 7 and 8, 6 has a higher probability of trap formation due to a higher local concentration of dye molecules and shorter distances between them. As a consequence, the excitation energy is delivered rapidly (within 23 ps) to the traps, resulting in decreases of the fluorescence, intersystem crossing, and singlet oxygen quantum yields in comparison with the values of the reference compounds.

Effect of ferrocene-substituted porphyrin RL-91 on Candida albicans biofilm formation - Lippert, Rainer; Vojnovic, Sandra; Mitrovic, Aleksandra; Jux, Norbert; Ivanovic-Burmazovic, Ivana; Vasiljevic, Branka; Stankovic, Nada (Bioorganic and Medicinal Chemistry Letters, 2014)
Ferrocene-substituted porphyrin RL-91 exhibits antifungal activity against opportune human pathogen Candida albicans. RL-91 efficiently inhibits growth of both planktonic C. albicans cells and cells within biofilms without photoactivation. The minimal inhibitory concentration for plankton form (PMIC) was established to be 100 μg/mL and the same concentration killed 80% of sessile cells in the mature biofilm (SMIC80). Furthermore PMIC of RL-91 efficiently prevents C. albicans biofilm formation. RL-91 is cytotoxic for human fibroblasts in vitro in concentration of 10 μg/mL, however it does not cause hemolysis in concentrations of up to 50 μg/mL. These findings open possibility for application of RL-91 as an antifungal agent for external antibiofilm treatment of medical devices as well as a scaffold for further development of porphyrin based systemic antifungals. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Antifungal; Biofilm; Candida albicans; Ferrocene; Porphyrins

Efficient synthetic access to cationic dendrons and their application for ZnO nanoparticles surface functionalization: New building blocks for dye-sensitized solar cells - Gnichwitz, Jan-Frederik; Marczak, Renata; Werner, Fabian; Lang, Nina; Jux, Norbert; Guldi, Dirk Michael; Peukert, Wolfgang; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A new concept for the efficient synthesis of cationic dendrons, 4-tert-butyl-1-(3-(3,4-dihydroxybenzamido)benzyl)pyridinium bromide (17), 1,1′-(5-(3,4-dihydroxybenzamido)-1,3-phenylene)bis(methylene) bis(4-tert-butylpyridinium) bromide (18), N1,N7-bis(3-(4-tert-butyl-pyridium- methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenyl-amino) -3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (19), and N1,N7-bis(3,5-bis(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3, 5-bis(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3, 4-dihydroxybenzamido)heptanediamide hexabromide (20), and their facile binding to zinc oxide (ZnO) nanostructures is introduced. Dendrons containing highly reactive benzylic bromides reacted readily with 4-tert-butyl-pyridine and resulted in cationic dendrons. Furthermore, these permanently positively charged dendrons were equipped with a catechol anchor group. This enabled ZnO surface functionalization by simple immersion. The adsorption of 17, 18, 19, and 20 on the colloidal nanoparticles was monitored by Langmuir isotherms. The highest obtained experimental loadings correspond to 99.5%, 98.6%, 99.1%, and 42.5% of the particle surface for 17, 18, 19, and 20, respectively. These results indicate insufficient adsorption of the largest molecule 20 leading to reduced colloidal stability of the nanoparticles, while an enhanced stability after grafting with 17, 18, and 19 was observed. Mesoporous films suitable for the use as electrodes in dye-sensitized solar cells (DSSCs) were prepared. Subsequently, the films were functionalized with 18, 19, or 20 and sensitized with zinc-5,15-bis-[2′,6′-bis-2″,2″-bis-(carboxy)- ethyl-methyl-4′-tert-butyl-pheny]-10,20-bis-(4′-tert-butylphenyl) porphyrin-octasodium-salt. UV-vis absorption spectra confirmed that 18, 19, and 20 are suitable for the stable electrostatic attachment of the dye. Current-voltage characteristics of complete cells demonstrated that increasing positive functionalization of the ZnO surface leads to decreased open circuit voltages (V ). All V values were around 0.4 V with a maximum for the 18 functionalized ZnO film of 0.45 V. The maximum cell efficiency obtained (0.31%) is rather high, considering the narrow spectral absorption of the dye and the rather thin ZnO films used. Finally, incident photon to current efficiency (IPCE) measurements confirmed photoinduced electron injection from the dye. These features are important assets for applications in particle technology and even facilitated advanced devices like a supramolecular DSSC complete with a subsequent layer of negatively charged porphyrins. © 2010 American Chemical Society.

Electron accepting porphycenes on graphene - Costa, Ruben Dario; Malig, Jenny; Brenner, Wolfgang; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2013)
The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electronic Communication across Porphyrin Hexabenzocoronene Isomers - Martin, Max; Lungerich, Dominik; Haines, Philipp; Hampel, Frank; Jux, Norbert (Angewandte Chemie International Edition, 2019)
Single-molecule electronic components (SMECs) are envisioned as next-generation building blocks in quantum circuit systems. However, challenges such as the reproducibility of the electrode attachment to the individual molecules hamper their fundamental investigation. For our purpose, we introduced quasi optoelectronic electrodes (QOEs) that allow for rapid investigations of the properties and suitability of compounds for molecular electronic devices. In particular, we probed hexa-peri-hexabenzocoronene (HBC) as a model system for D6h-symmetrical nanographenes, with porphyrins as QOEs attached to the periphery. We prepared selectively bis-porphyrin-functionalized HBCs with ortho-, meta- and para-substitution and studied their communication properties, in correlation to the geometrical alignment and size of the system, by electrochemistry and optical spectroscopy. Further insights into structure–property relationships were gained by DFT calculations and X-ray diffraction analysis.
CRIS-Team Scopus Importer:2019-06-04
Keywords: exchange interactions; hydrocarbons; molecular electronics; porphyrinoids; UV/Vis spectroscopy

Electrophoresis of electrostatically assembled fullerene-porphyrin conjugates - Hartnagel, Uwe; Balbinot, Domenico; Jux, Norbert; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2006)
The formation of electrostatically coupled assemblies of a series of anionic dendritic fullerene derivatives and cationic porphyrins in buffered aqueous media was studied with gel electrophoresis. Of central interest in these investigations was the variation of the amount of charge carried by the molecules, their size, shape and self-aggregation. Ferric cytochrome c 1 and the more rigid zinc porphyrin 2 served as octacationic species. The two new anionic fullerene derivates 3 and 6 were synthesized. The formation of electrostatic complexes of the fullerene polyelectrolytes 3 and 4 with 1 and 2 was clearly evident in the gel electrophoresis experiment. Compounds 5 and 6 showed a similar behaviour towards 2. The electrophoresis experiments confirmed previous results obtained with other techniques on a qualitative level and gave new insights into aggregation phenomena. © The Royal Society of Chemistry 2006.

Electrostatic assemblies of fullerene-porphyrin hybrids: Toward long-lived charge separation - Balbinot, Domenico; Atalick, Stefan; Guldi, Dirk Michael; Hatzimarinaki, Maria; Hirsch, Andreas; Jux, Norbert (Journal of Physical Chemistry B, 2003)
The Coulomb complex formation of a dendritic fullerene oligocarboxylate (1) and an octapyridinium zinc porphyrin salt (ZnP) was investigated. A Job plot obtained by monitoring the Soret absorption of ZnP upon addition of 1 in a phosphate buffer (pH 7.2, ionic strength = 0.012) indicated the formation of a 1:1 complex, ZnP/1, for which an association constant of (3.5 ± 1.0) × 10 M was determined. Parallel fluorescence titration experiments revealed that the ZnP emission is strongly quenched in the ZnP/1 complex. In particular, the noted decrease of fluorescence intensity in ZnP with variation of 1 and evidence for a new short-lived emissive component suggest a static quenching event inside a ZnP/1 complex. From the fluorescence titration, a value of (1.1 ± 0.1) × 10 M for the association constant of the ZnP/1 complex at pH 7.2 was derived. The association constant decreased, however, when the ionic strength of the solution was raised. Electron-transfer quenching was confirmed by transient absorption spectroscopy, which showed the fingerprint absorptions of the ZnP radical cation and the 1 radical anion and a lifetime of 1.1 μs for the charge-separated state. Molecular dynamic simulations offer insight into the supramolecular structure of the fullerene-porphyrin hybrid, ZnP/1.

Experimental and Theoretical Structure Elucidation of the [2 : 1] Complex Ion of Carbo[n]helicene with n=6, 7 and 8 and Ag+ - Oschwald, Johannes; Reger, David; Frühwald, Stefan; Warmbrunn, Vera; Görling, Andreas; Jux, Norbert; Drewello, Thomas (ChemPhysChem, 2023)
Gas-phase complexes of [n]helicenes with n=6, 7 and 8 and the silver(I) cation are generated utilizing electrospray ionization mass spectrometry (ESI-MS). Besides the well-established [1 : 1] helicene/Ag+-complex in which the helicene provides a tweezer-like surrounding for the Ag+, there is also a [2 : 1] complex formed. Density functional theory (DFT) calculations in conjunction with energy-resolved collision-induced dissociation (ER-CID) experiments reveal that the second helicene attaches via π-π stacking to the first helicene, which is part of the pre-formed [1 : 1] tweezer complex with Ag+. For polycyclic aromatic hydrocarbons (PAHs) of planar structure, the [2 : 1] complex with silver(I) is typically structured as an Ag+-bound dimer in which the Ag+ would bind to both PAHs as the central metal ion (PAH–Ag+–PAH). For helicenes, the Ag+-bound dimer is of similar thermochemical stability as the π-π stacked dimer, however, it is kinetically inaccessible. Coronene (Cor) is investigated in comparison to the helicenes as an essentially planar PAH. In analogy to the π-π stacked dimer of the helicenes, the Cor−Ag+−Cor−Cor complex is also observed. Competition experiments using [n]helicene mixtures reveal that the tweezer complexes of Ag+ are preferably formed with the larger helicenes, with n=6 being entirely ignored as the host for Ag+ in the presence of n=7 or 8.
CRIS-Team Scopus Importer:2023-09-15
Keywords: carbo[n]helicenes; density functional calculations; Energy-resolved CID; tweezer; [2 : 1] helicene/silver(I) complex ion

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

Four-Step Domino Reaction Enables Fully Controlled Non-Statistical Synthesis of Hexaarylbenzene with Six Different Aryl Groups** - Grau, Benedikt; Dill, Maximilian; Hampel, Frank; Kahnt, Axel; Jux, Norbert; Tsogoeva, Svetlana (Angewandte Chemie International Edition, 2021)
Hexaarylbenzene (HAB) derivatives are versatile aromatic systems playing a significant role as chromophores, liquid crystalline materials, molecular receptors, molecular-scale devices, organic light-emitting diodes and candidates for organic electronics. Statistical synthesis of simple symmetrical HABs is known via cyclotrimerization or Diels-Alder reactions. By contrast, the synthesis of more complex, asymmetrical systems, and without involvement of statistical steps, remains an unsolved problem. Here we present a generally applicable synthetic strategy to access asymmetrical HAB via an atom-economical and high-yielding metal-free four-step domino reaction using nitrostyrenes and alpha,alpha-dicyanoolefins as easily available starting materials. Resulting domino product-functionalized triarylbenzene (TAB)-can be used as a key starting compound to furnish asymmetrically substituted hexaarylbenzenes in high overall yield and without involvement of statistical steps. This straightforward domino process represents a distinct approach to create diverse and still unexplored HAB scaffolds, containing six different aromatic rings around central benzene core.
CRIS-Team WoS Importer:2021-09-03

Fullerene-pyropheophorbide a complexes as sensitizer for photodynamic therapy: Uptake and photo-induced cytotoxicity on Jurkat cells - Rancan, Fiorenza; Helmreich, Matthias; Mölich, Andreas; Jux, Norbert; Hirsch, Andreas; Röder, Beate; Witt, Christian; Böhm, Fritz (Journal of Photochemistry and Photobiology B-Biology, 2005)
The main challenge in searching for new photosensitizers is to improve their specificity for target cells to avoid toxicity towards normal cells. New modular drug delivery systems were proposed consisting of a multiplying unit with the property of carrying several drug moieties and an addressing unity with high selectivity for target cells. Following this concept, two new fullerene-bis-pyropheophorbide a derivatives were synthesized: a mono-(FP1) and a hexa-adduct (FHP1). The photophysical characterization of the compounds revealed significantly different parameters related to the number of addends at the fullerene core. In this study, the derivatives were tested with regard to their intracellular uptake and photosensitizing activity towards human leukemia T-lymphocytes (Jurkat cells) in comparison with the free sensitizer, pyropheophorbide a. The C -hexa-adduct FHP1 resulted to have a significative phototoxic activity (58% dead cell, after a dose of 400 mJ/cm , 688 nm) while the mono-adduct FP1 had a very low phototoxicity and only at higher light doses. The photosensitizing activity of the fullerene hexa-adduct, FHP1, resulted to be lower than that of pyropheophorbide a. The lesser intracellular concentration reached by the C -hexa-adduct FHP1 is probably the reason for its lower phototoxicity with respect to pyropheophorbide a. © 2005 Elsevier B.V. All rights reserved.

Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

Gas-Phase Transformation of Fluorinated Benzoporphyrins to Porphyrin-Embedded Conical Nanocarbons - Lungerich, Dominik; Hitzenberger, Jakob; Ruppel, Michael; Döpper, Tibor; Witt, Matthias; Ivanovic-Burmazovic, Ivana; Görling, Andreas; Jux, Norbert; Drewello, Thomas (Chemistry - A European Journal, 2020)
Geodesic nitrogen-containing graphene fragments are interesting candidates for various material applications, but the available synthetic protocols, which need to overcome intrinsic strain energy during the formation of the bowl-shaped skeletons, are often incompatible with heteroatom-embedded structures. Through this mass spectrometry-based gas-phase study, we show by means of collision-induced dissociation experiments and supported by density functional theory calculations, the first evidence for the formation of a porphyrin-embedded conical nanocarbon. The influences of metalation and functionalization of the used tetrabenzoporphyrins have been investigated, which revealed different cyclization efficiencies, different ionization possibilities, and a variation of the dissociation pathway. Our results suggest a stepwise process for HF elimination from the fjord region, which supports a selective pathway towards bent nitrogen-containing graphene fragments.
CRIS-Team Scopus Importer:2020-09-11
Keywords: annulenes; collision-induced dissociation; C−F activation; mass spectrometry; polycyclic aromatic hydrocarbons; porphyrinoids

HBC-porphyrin-close contact chromophores - Englert, Jan; Malig, Jenny; Zamolo, Valeria Anna; Hirsch, Andreas; Jux, Norbert (Chemical Communications, 2013)
A photo/redoxactive hexa-peri-hexabenzocoronene-porphyrin conjugate with a direct connection between the two chromophores was synthesised using a formylated hexaphenylbenzene precursor. © 2013 The Royal Society of Chemistry.

Hexa-: Peri-hexabenzocoronene decorated with an allenylidene ruthenium complex-Almost a flyswatter - Lorenz, Rebecca; Reger, David; Weller, Ruth; Jux, Norbert; Burzlaff, Nicolai (Dalton Transactions, 2020)
Carbon-rich ruthenium allenylidene complexes bearing either a hexaarylbenzene (HAB) or a hexa-peri-hexabenzocoronene (HBC) substituent were synthesised. This was achieved via the corresponding propargyl alcohols with HAB and HBC substituents, which were accessible via 3 or 4 step reaction cascades. Reaction of the propargyl alcohols HCC(OH)Ph(HAB) and HCC(OH)Ph(HBC) with [RuCl(η5-C5H5)(PPh3)2] yielded the complexes [Ru(η5-C5H5)(CCC(HAB)(Ph))(PPh3)2]PF6 and [Ru(η5-C5H5)(CCC(HBC)(Ph))(PPh3)2]PF6. The latter of which shows interesting π-π-stacking behaviour in the solid state as well as aggregation in solution.
CRIS-Team Scopus Importer:2020-10-16

Highly Regioselective Alkylation of Hexabenzocoronenes: Fundamental Insights into the Covalent Chemistry of Graphene - Holzwarth, Johannes; Amsharov, Konstantin; Sharapa, Dmitry; Reger, David; Roshchyna, Kateryna; Lungerich, Dominik; Jux, Norbert; Hauke, Frank; Clark, Timothy; Hirsch, Andreas (Angewandte Chemie International Edition, 2017)
Keywords: alkylation; density-functional calculations; graphene; radicals; reaction mechanisms

Improving photocurrent generation: Supramolecularly and covalently functionalized single-wall carbon nanotubes-polymer/porphyrin donor-acceptor nanohybrids - Rahman, Aminur; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Jux, Norbert; Tchoul, Maxim N.; Ford, Warren T.; Mateo-Alonso, Aurelio; Prato, Maurizio (Chemistry - A European Journal, 2008)
Novel nanohybrids based on covalently and noncovalently functionalized single-wall carbon nanotubes (SWNTs) have been prepared and assembled for the construction of photoactive electrodes. Polymer-grafted SWNTs were synthesized by free-radical polymerization of (vinylbenzyl)trimethylammonium chloride. Poly[(vinylbenzyl)trimethylammonium chloride] (PVBTA) was also noncovalently wrapped around SWNTs to form stable, positively charged SWNT/PVBTA suspensions in water. Versatile donor-acceptor nanohybrids were prepared by using the electrostatic/van der Waals interactions between covalent SWNT-PVBTA and/or noncovalent SWNT/PVBTA and porphyrins (HP and/or ZnP ). Several spectroscopic, microscopic, transient, and photoelectrochemical measurements were taken to characterize the resulting supramolecular complexes. Photoexcitation of the nanohybrids afforded long-lived radical ion pairs with lifetimes as long as 2.2 us. In the final part, photoactive electrodes were constructed by using a layer-by-layer technique on an indium tin oxide covered glass support. Photocurrent measurements gave remarkable internal photon-to-current efficiencies of 3.81 and 9.90% for the covalent ZnP-/SWNT-PVBTA and noncovalent ZnP /SWNT/PVBTA complex, respectively, when a potential of 0.5 V was applied. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Influence of an extremely negatively charged porphyrin on the reversible binding kinetics of NO to Fe(III) and the subsequent reductive nitrosylation - Jee, Joo-Eun; Eigler, Siegfried; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2007)

Inside Back Cover: Zinc Porphyrin Metal-Center Exchange at the Solid–Liquid Interface (Chem. Eur. J. 25/2016) - Franke, Matthias; Marchini, Florencia; Jux, Norbert; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Chemistry - A European Journal, 2016)
Keywords: ion exchange; metalation; porphyrins; solid–liquid interfaces; zinc

Insights in the Reaction Mechanistics: Isotopic Exchange During the Metalation of Deuterated Tetraphenyl-21,23D-porphyrin on Cu(111) - Röckert, Michael; Franke, Matthias; Tariq, Quratulain; Lungerich, Dominik; Jux, Norbert; Stark, Michael Werner; Kaftan, Andre; Ditze, Stefanie; Marbach, Hubertus; Laurin, Mathias; Libuda, Jörg; Steinrück, Hans-Peter; et al. (Journal of Physical Chemistry C, 2014)
Using temperature-programmed desorption (TPD), the self-metalation and dehydrogenation of deuterated 5,10,15,20-tetraphenyl-21,23D-porphyrin on Cu(111) has been studied, resulting in new insight into the metalation of porphyrins on surfaces. The metalation is found to proceed through the transfer of the central aminic hydrogen atoms to the Cu(111) surface and not, as suggested by gas phase calculations, through the combination of the hydrogen atoms to molecular hydrogen above the partially inserted metal center. This finding suggests that the metalation reaction could be significantly influenced by the stability of hydrogen on the substrate surface. The metalation reaction and the subsequent hydrogenation and dehydrogenation of theperiphery of the porphyrin molecule leading to hydrogen-deuterium exchange are modeled with a simple microkinetic reaction model. The model is able to d escribe the main features of the TPD spectra.

Integrating metalloporphycenes into p-type NiO-based dye-sensitized solar cells - Feihl, Sebastian; Costa, Ruben D.; Brenner, Wolfgang; Margraf, Johannes; Casillas Pacheco, Ruben; Langmar, Oliver; Browa, Anne; Shubina, Tatyana; Jux, Norbert; Guldi, Dirk Michael; Clark, Timothy (Chemical Communications, 2014)
In the current work, we have explored a novel synthetic route towards metalated porphycenes and their use in p-type NiO-based dye-sensitized solar cells. Particular emphasis is placed on the influence that the relative positioning of the anchoring group exerts on the DSSC performance.

Integrating water-soluble graphene into porphyrin nanohybrids - Malig, Jenny; Nieto, Carlos Romero; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2012)
Exfoliation of graphite by a positively charged pyrene derivative was achieved in water and electronic communication by non-invasive electrostatic interaction with a negatively charged porphyrin was accomplished and proven photospectroscopically. The oppositely charged components were assembled through layer by layer deposition. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Interaction of cobalt(II) tetraarylporphyrins with a Ag(111) surface studied with photoelectron spectroscopy - Jux, Norbert; Maier, Florian; Steinrück, Hans-Peter; et al. (Journal of Physical Chemistry C, 2007)
The interaction of cobalt(II) tetraphenylporphyrin (CoTPP) and cobalt(II) tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (CoTTBPP) with a Ag(111) surface has been investigated with photoelectron spectroscopy (XPS/ UPS). It is demonstrated that these adsorbed metal complexes are excellent model systems for studying the electronic interaction between a coordinated metal ion and a metal surface. The photoelectron spectra and work function data provide evidence that the electronic interaction between the cobalt ion and the silver surface results in a transfer of electron density from the surface to the ion. The presence of an additional electronic state located ∼1 eV above the singly occupied molecular orbital (SOMO) of the metalloporphyrins is consistent with a molecular orbital (MO) model of the Co-Ag interaction as is the fact that the energetic position of this state depends on the distance between the Co ion and the Ag surface. The adsorbate-induced work function changes for the saturated monolayers amount to -0.72 eV for CoTPP and -0.91 eV for CoTTBPP. For comparison, we also present data of monolayer films of tetraphenylporphyrin and zinc(II) tetraphenylporphyrin. © 2007 American Chemical Society.

Intracellular uptake and phototoxicity of 31,3 2-didehydrophytochlorin-fullerene hexaadducts - Rancan, Fiorenza; Helmreich, Matthias; Mölich, Andreas; Jux, Norbert; Hirsch, Andreas; Röder, Beate; Böhm, Fritz (Photochemistry and Photobiology, 2007)
C-fullerene derivatives are potential building blocks in modular carrier systems for selective tumor targeting. In [5:1] fullerene hexakis adducts, one position can be occupied by an addressing unit (e.g. monoclonal antibody) while the other five positions are suitable for dendrimers or spacers loaded with several drug moieties. This article reports intracellular uptake and phototoxicity of three fullerene hexakis adducts coupled with a different number of photosensitizers: a bis(3,3- didehydrophytochlorin)-fullerene [5:1]-hexaadduct (FHP1), a fullerene [5:1]-hexaadduct with six 3,3-didehydrophytochlorin groups (FHP6) and a fullerene [6:0]-hexaadduct that carries 12 3 ,3-didehydrophytochlorin units (FHP12). The most promising complex, the hexa-3,3-didehydrophytochlorin fullerene hexaadduct FHP6, was also compared with its fullerene-free analogous derivative P6. It was found that the extent of intracellular uptake is influenced by both nanomolecular size and asymmetry (amphiphilicity) of the fullerene complexes. The degree and mechanism of phototoxicity was found to depend on intracellular concentrations and singlet oxygen quantum yields. © 2007 The Authors.

Investigations of Low-Symmetrical Tetraaryltetrabenzoporphyrins Produced by Mixed Condensation Reactions - Ruppel, Michael; Gazetas, Lampros-Pascal; Lungerich, Dominik; Hampel, Frank; Jux, Norbert (Journal of Organic Chemistry, 2020)
Within the past decade, tetraaryltetrabenzoporphyrins (TATBPs) have gained rising attention due to their potential in various fields of materials science and medicinal chemistry. However, this class of compounds still lacks in structural diversity, especially in the case of low-symmetrical compounds. Herein, mixed condensations were utilized to generate TATBPs with different substituents either in the meso-positions or the periphery of the macrocycle with total yields of 55-58%. The separation of crude mixtures was achieved by feasible chromatographic purification. The influence of symmetry on the electronic properties of TATBPs was studied by optical spectroscopy, electrochemistry, and X-ray diffraction.
CRIS-Team WoS Importer:2020-07-17

Iron(III) complex of a crown ether-porphyrin conjugate and reversible binding of superoxide to its iron(II) form - Dürr, Katharina L.; Macpherson, Brendan P.; Warratz, Ralf; Hampel, Frank; Tuczek, Felix; Helmreich, Matthias; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Journal of the American Chemical Society, 2007)
The synthesis and characterization of the Fe(III) complex of a novel crown ether-porphyrin conjugate, 5-N-(4-aza-18-crown-6)methyl-5 ,10,15,20-tetra-tert-butyl- 5-methyl-5,10,15,20-tetraphenylporphyrin (HPorph), as well as the corresponding hydroxo, dimeric, Fe(II), and peroxo species are reported. The crystal structure of [Fe(Porph)Cl]·H O·FeCl·C H·EtOH is also reported. [Fe(Porph) (DMSO)] and K[Fe(Porph)(O)] are high-spin species (Mössbauer data: δ = 0.38 mm s, ΔE = 0.83 mm s and δ = 0.41 mm s, ΔE = 0.51 mm s, respectively), whereas in a solution of reduced [Fe(Porph)-(DMSO) ] complex the low-spin [Fe(Porph)(DMSO) ] (δ = 0.44 mm s, ΔE = 1.32 mm s) and high-spin [Fe(Porph)(DMSO)] (δ = 1.27 mm s ΔE = 3.13 mm s) iron(II) species are observed. The reaction of [Fe(Porph)(DMSO)] with KO in DMSO has been investigated. The first reaction step, involving reduction to [Fe(Porph)(DMSO) ], was not investigated in detail because of parallel formation of an Fe-(III)-hydroxo species. The kinetics and thermodynamics of the second reaction step, reversible binding of superoxide to the Fe(II) complex and formation of an Fe(III)-peroxo species, were studied in detail (by stopped-flow time-resolved UV/vis measurements in DMSO at 25°C), resulting in k = 36 500 ± 500 M s, k = 0.21 ± 0.01 s (direct measurements using an acid as a superoxide scavenger), and K = (1.7 ± 0.2) × 10 (superoxide binding constant kinetically obtained as k/k), (1.4 ± 0.1) × 10, and (9.0 ± 0.1) × 10 M (thermodynamically obtained in the absence and in the presence of 0.1 M NBuPF , respectively). Temperature-dependent kinetic measurements for k (-40 to 25°C in 3:7 DMSO/CHCN mixture) yielded the activation parameters ΔH = 61.2 ± 0.9 kJ mol and ΔS = +48 ± 3 J K mol. The observed reversible binding of superoxide to the metal center and the obtained kinetic and thermodynamic parameters are unique. The finding that fine-tuning of the proton concentration can cause the Fe(III)-peroxo species to release O and form an Fe(II) species is of biological interest, since this process might occur under very specific physiological conditions. © 2007 American Chemical Society.

Kinetic and mechanistic studies on the reaction of nitric oxide with a water-soluble octa-anionic iron(III) porphyrin complex - Eigler, Siegfried; Hampel, Frank; Jux, Norbert; Wolak, Maria; Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2005)
The polyanionic water-soluble and non-μ-oxo-dimer-forming iron porphyrin iron(III) 5,10,15,20-tetra- tert-butyl-5,5,15,15-tetrakis[2, 2-bis(carboxylato)ethyl]-5,10,15,20-tetraphenylporphyrin, (P) Fe (1), was synthesized as an octasodium salt by applying well-established porphyrin and organic chemistry procedures to bromomethylated precursor porphyrins and characterized by standard techniques such as UV-vis and H NMR spectroscopy. A single pK value of 9.26 was determined for the deprotonation of coordinated water in (P)Fe (HO) (1-H2O) present in aqueous solution at pH <9. The porphyrin complex reversibly binds NO in aqueous solution to give the mononitrosyl adduct, (P)Fe(NO )(L), where L = HO or OH. The kinetics of the binding and release of NO was studied as a function of pH, temperature, and pressure by stopped-flow and laser flash photolysis techniques. The diaqua-ligated form of the porphyrin complex binds and releases NO according to a dissociative interchange mechanism based on the positive values of the activation parameters ΔS and ΔV for the "on" and "off" reactions. The rate constant k = 6.2 × 10 M s (24°C), determined for NO binding to the monohydroxo-ligated (P)Fe(OH) (1-OH) present in solution at pH >9, is markedly lower than the corresponding value measured for 1-HO at lower pH (k = 8.2 × 10 M s , 24°C, pH 7). The observed decrease in the reactivity is contradictory to that expected for the diaqua- and monohydroxo-ligated forms of the iron(III) complex and is accounted for in terms of a mechanistic changeover observed for 1-HO and 1-OH in their reactions with NO. The mechanistic interpretation offered is further substantiated by the results of water-exchange studies performed on the polyanionic porphyrin complex as a function of pH, temperature, and pressure. © 2005 American Chemical Society.

Laterally π-Extensed Nitrogen-Doped Molecular Nanographenes – From Anti-Kasha Emission to Ping-Pong Energy Transfer Events - Beneventi, Giovanni Mariano; Schöll, Kilian; Platzer, Benedikt; Krug, Marcel; Mai, Lukas; Negri, Fabrizia; Cadranel, Alejandro; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2024)
Nanographenes, which feature at least one dimension smaller than 100 nm, are drawing interdisciplinary attention. Understanding the interplay between structure and properties is, however, still in its infancy. Molecular nanographenes are much better suited to fill this knowledge gap than graphene quantum dots or nanoribbons. Their bottom-up synthesis allows atomic precision and, thereby, assists in handling structure and connecting it with properties. Herein, the effects of nitrogen-doping and lateral π-extension in molecular nanographenes and in their coordination complexes with ruthenium porphyrins are investigated. The presence of just nitrogen resulted in an increase of the fluorescence quantum yield, without, however, affecting the energy levels. Lateral π-extension of the nanographenes, instead, resulted in a modulation of the excited states energy, which leads to a thermally-activated dual fluorescence with quantum yields as high as 61%. In the corresponding coordination complexes, lateral π-extension resulted in a ping-pong energy transfer cascade, that is, from the nanographene to the metalloporphyrin and back to the nanographene. The results help to directly rationalize properties observed in both graphene quantum dots and nanoribbons. Moreover, they prove that molecular nanographenes are appealing components for solar energy conversion schemes, where the modulation of inter-component energy transfer is of utmost importance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: anti-Kasha emission; coordination complexes; energy transfer; metalloporphyrin; molecular nanographenes

Layer-by-layer deposition of molecular oligoelectrolytes-investigation of assembling and degradation behaviour - Rosenlehner, Karin; Schunk, Torsten; Jux, Norbert; Brettreich, Michael; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2008)
The assembly and degradation behavior of oligoelectrolyte multilayer films (OEMs) self assembled by layer-by-layer deposition of positively and negatively charged oligoelectrolytes 1-6 was investigated. Next to colorless oligoelectrolytes we have employed representatives involving chromophores, in particular porphyrins. This allows for the systematic observation of both assembly and disassembly of the OEMs using optical spectroscopy, where chromophore containing building blocks serve as reporter electrolytes. The OEMs investigated in this study were built in a consistent, monomolecular matter and show linear correlation between the absorption and the number of layers. Using the concept of reporter electrolytes we have introduced for the first time also the use of non-chromophoric oligoelectrolytes, such as the new synthesized cationic system 2 as building blocks for OEMs. Moreover, we have investigated for the first time the degradation behavior of OEMs. We demonstrated that two different mechanisms of degradation proceed at the same time. The direct degradation is accompanied by a second release mechanism. © The Royal Society of Chemistry.

Manifold-Fused Porphyrin-Nanographene Conjugates - Oleszak, Christoph; Ritterhoff, Christian; Martin, Max; Meyer, Bernd; Jux, Norbert (Chemistry - A European Journal, 2024)
A library of novel π-extended porphyrin-hexabenzocoronene (HBC) architectures is presented. Two distinct synthetic pathways were utilized to obtain either phenyl- or HBC-fused compounds. Absorption experiments reveal the species’ exciting photophysical and optoelectronic properties. Depending on the degree of π-extension, the number of porphyrins, and their relative position, a decisive change in shape, panchromatic broadening, and red-shifting of the absorption curves is observed. Theoretical studies give more profound insight into the molecule's electronic structures, showing vast decreases in HOMO-LUMO energy gaps.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-Extension

Metalation and coordination reactions of 2H-meso-trans-di(p-cyanophenyl) porphyrin on Ag(111) with coadsorbed cobalt atoms - Kuliga, Jan; Zhang, Liang; Lepper, Michael; Lungerich, Dominik; Hölzel, Helen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2018)
We investigated the metalation and coordination reactions of Co with 2H-5,15-bis(para-cyanophenyl)10,20-bisphenylporphyrin (2HtransDCNPP) on a Ag(111) surface by scanning tunneling microscopy. At room temperature (RT), 2HtransDCNPPs self-assemble into a supramolecular structure stabilized by intermolecular hydrogen bonding. The metalation of 2HtransDCNPP is achieved either by depositing Co atoms onto the supramolecular structure at RT, or, alternatively, by depositing the molecules onto a submonolayer Co-precovered Ag(111) surface with a subsequent heating to 500 K. In addition, the molecules coordinate to Co atoms through the N atoms in the peripheral cyano groups with a preference of isolated 4-fold coordination motifs at RT.

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan; De Campos Ferreirra, Rodrigo Cezar; Adhikari, Rajan; Massicot, Stephen; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Marbach, Hubertus; De Siervo, Abner; Steinrück, Hans-Peter (ChemPhysChem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20-terakis(4-cyanophenyl)porphyrin (2HTCNPP) with post-deposited Zn atoms and the targeted reaction product Zn-5,10,15,20-terakis(4-cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post-deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post-deposited Zn. We attribute this to metastable SAT ("sitting atop") complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.
CRIS-Team WoS Importer:2021-01-29

Multicomponent redox gradients on photoactive electrode surfaces - Guldi, Dirk Michael; Zilbermann, Israel; Anderson, Greg; Lin, Andrew; Balbinot, Domenico; Jux, Norbert; Hatzimarinaki, Maria; Hirsch, Andreas; Prato, Maurizio (Chemical Communications, 2004)
Redox gradients have been used to tailor the arrangement of photoactive ITO-electrodes at the molecular level.

Multiple-Porphyrin Functionalized Hexabenzocoronenes - Martin, Max; Lungerich, Dominik; Hampel, Frank; Langer, Jens; Ronson, Tanya K.; Jux, Norbert (Chemistry - A European Journal, 2019)
Porphyrin–hexabenzocoronene architectures serve as good model compounds to study light-harvesting systems. Herein, the synthesis of porphyrin functionalized hexa-peri-hexabenzocoronenes (HBCs), in which one or more porphyrins are covalently linked to a central HBC core, is presented. A series of hexaphenylbenzenes (HPBs) was prepared and reacted under oxidative coupling conditions. The transformation to the respective HBC derivatives worked well with mono- and tri-porphyrin-substituted HPBs. However, if more porphyrins are attached to the HPB core, Scholl oxidations are hampered or completely suppressed. Hence, a change of the synthetic strategy was necessary to first preform the HBC core, followed by the introduction of the porphyrins. All products were fully characterized, including, if possible, single-crystal XRD. UV/Vis absorption spectra of porphyrin-HBCs showed, depending on the number of porphyrins as well as with respect to the substitution pattern, variations in their spectral features with strong distortions of the porphyrins’ B-band.
CRIS-Team Scopus Importer:2019-11-19
Keywords: hexabenzocoronene; nanographene; nanostructures; porphyrinoids; Scholl oxidation

On the adsorption of different tetranaphthylporphyrins on Cu(111) and Ag(111) - Brox, Jan; Adhikari, Rajan; Shaker, Majid; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Jaekel, Simon; Steinrück, Hans-Peter (Surface Science, 2022)
We address the adsorption of 2H-tetranaphthylporphyrin (2HTNP) and 2H-tetranaphthylbenzoporphyrin (2HTNBP) on Cu(111) and Ag(111). The difference between the two molecules is that for 2HTNBP the pyrrole groups are replaced by isoindole groups. We were interested in the resulting differences in the adsorption behavior on the two surfaces, in particular the role of the naphthyl groups. The investigations are performed with scanning tunneling microscopy at room temperature (RT) and after heating treatments (500 and 600 K). On Ag(111), 2HTNP forms a commensurable superstructure at RT, which transforms to a denser packed, non-commensurable structure upon annealing. For 2HTNBP, individual molecules are observed on Cu(111) at RT, which exhibit different mobility. In contrast, on Ag(111) the formation of ordered 2HTNBP islands occurs, which are stabilized by T-type interactions. After heating to 500 K, these islands undergo a structural change to a denser packed structure, which is stabilized by π-π stacking of neighboring naphthyl groups.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Commensurability; Naphthyl functionalization; Porphyrins; Self-assembly; STM

On the critical role of the substrate: the adsorption behaviour of tetrabenzoporphyrins on different metal surfaces - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Menzel, Teresa; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2017)
The adsorption behaviour of 2H-5,10,15,20-tetraphenyltetrabenzoporphyrin (2HTPTBP) on different metal surfaces, i.e., Ag(111), Cu(111), Cu(110), and Cu(110)-(2 x 1)O was investigated by scanning tunnelling microscopy at room temperature. The adsorption of 2HTPTBP on Ag(111) leads to the formation of a well-ordered two-dimensional (2D) island structure due to the mutual stabilization through the intermolecular pi-pi stacking and T-type-like interactions of phenyl and benzene substituents of neighboring molecules. For 2HTPTBP on Cu(111), the formed 2D supramolecular structures exhibit a coverage-dependent behaviour, which can be understood from the interplay of molecule-substrate and molecule-molecule interactions. In contrast, on Cu(110) the 2HTPTBP molecules form dispersed one-dimensional (1D) molecular chains along the [1 (1) over bar0] direction of the substrate due to relatively strong attractive molecule-substrate interactions. Furthermore, we demonstrate that the reconstruction of the Cu(110) surface by oxygen atoms yields a change in dimensionality of the resulting nanostructures from 1D on Cu(110) to 2D on (2 x 1) oxygen-reconstructed Cu(110), induced by a decreased molecule-substrate interaction combined with attractive molecule-molecule interactions. This comprehensive study on these prototypical systems enables us to deepen the understanding of the particular role of the substrate concerning the adsorption behavior of organic molecules on metal surfaces and thus to tweak the ordering in functional molecular architectures.

On the energetics of conformational switching of molecules at and close to room temperature - Ditze, Stefanie; Stark, Michael Werner; Buchner, Florian; Aichert, André; Jux, Norbert; Luckas, Nicola; Görling, Andreas; Hieringer, Wolfgang; Hornegger, Joachim; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of the American Chemical Society, 2014)
We observe and induce conformational switching of individual molecules via scanning tunneling microscopy (STM) at and close to room temperature. 2H-5,10,15,20-Tetrakis-(3,5-di-tert-butyl)-phenylporphyrin adsorbed on Cu(111) forms a peculiar supramolecular ordered phase in which the molecules arrange in alternating rows, with two distinct appearances in STM which are assigned to concave and convex intramolecular conformations. Around room temperature, frequent bidirectional conformational switching of individual molecules from concave to convex and vice versa is observed. From the temperature dependence, detailed insights into the energy barriers and entropic contributions of the switching processes are deduced. At 200 K, controlled STM tip-induced unidirectional switching is possible, yielding an information storage density of 4.9 × 10 bit/inch. With this contribution we demonstrate that controlled switching of individual molecules at comparably high temperatures is possible and that entropic effects can be a decisive factor in potential molecular devices at these temperatures. © 2014 American Chemical Society.

On the photophysics of nanographenes-investigation of functionalized hexa-: Peri -hexabenzocoronenes as model systems - Haines, Philipp; Reger, David; Träg, Johannes; Strauss, Volker; Lungerich, Dominik; Zahn, Dirk; Jux, Norbert; Guldi, Dirk Michael (Nanoscale, 2021)
In this study, we report on hexa-peri-hexabenzocoronenes (HBCs) as representative models for nanographenes. To this end, we synthesized a family of functionalized HBCs and investigated the impact of the substituents on the π-extended systems of the HBCs. DFT and TD-DFT calculations suggested a charge transfer character, which intensified as the electron density withdrawing effects of the substituents (-M-effect) increased. Unambiguous corroboration of the charge transfer character in the case of NO2-substituents was realized via steady-state absorption and fluorescence experiments, which focused on the dependencies on the solvent polarity and temperature featuring. Going beyond HBCs with NO2-substituents, time-correlated single photon counting, and femtosecond and nanosecond transient absorption spectroscopy unveiled long-lived singlet and triplet excited states. As a complement, we performed electrochemical and spectroelectrochemical measurements. These measurements were carried out to shed light onto the nature of the functionalized HBCs as electron acceptors and/or donors, on the one hand, and their corresponding spectroscopic signatures, on the other hand. All of the aforementioned information enabled intermolecular charge separation assays with, for example, suitable electron acceptors by steady-state and time-resolved spectroscopy. This journal is
CRIS-Team Scopus Importer:2021-02-05

Oxa[7]superhelicene: A pi-Extended Helical Chromophore Based on Hexa-peri-hexabenzocoronenes - Reger, David; Haines, Philipp; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2018)
A novel pi-extended "superhelicene" based on hexa-peri-hexabenzocoronenes (HBCs) has been synthesized by an efficient four-step synthetic procedure starting from diphenyl ether. Comprehensive structural analysis of the helicene was performed by NMR spectroscopy and mass spectrometry measurements together with X-ray analysis. Physicochemical analysis of the superhelicene and suitable HBC references revealed it had outstanding fluorescent features with quantum yields of over 80%.
Keywords: fluorescence; helical structures; photophysics; polycyclic aromatic hydrocarbons; pi-extension

Oxidative Cyclodehydrogenation Reactions with Tetraarylporphyrins - Martin, Max; Oleszak, Christoph; Hampel, Frank; Jux, Norbert (European Journal of Organic Chemistry, 2020)
The extension of the aromatic π-system of porphyrins is a powerful method to alter their optoelectronic properties. Herein, aryl substituents were fused to porphyrin cores by Scholl oxidation reactions that selectively produced mono- and doubly-fused porphyrins in yields of up to 69 %. Several different aryl substituents attached to the porphyrin were investigated with respect to their reactivity under Scholl conditions. The fused products were fully characterized, i.e., by UV/Vis absorption spectroscopy, which showed drastic changes in the electronic features. Insight into the solid-state behavior was obtained by X-ray crystallography. Our approach represents a novel option for the late-stage functionalization of porphyrin-based compounds.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-Extension

Panchromatic light funneling through the synergy in hexabenzocoronene-(metallo)porphyrin-fullerene assemblies to realize the separation of charges - Wolf, Maximilian; Lungerich, Dominik; Bauroth, Stefan; Popp, Maximilian; Platzer, Benedikt; Clark, Timothy; Anderson, Harry L.; Jux, Norbert; Guldi, Dirk Michael (Chemical Science, 2020)
Here, we present a novel butadiyne-linked HBC-ethynyl-porphyrin dimer, which exhibits in the ground state strong absorption cross sections throughout the UV and visible ranges of the solar spectrum. In short, a unidirectional flow of excited state energy from the HBC termini to the (metallo)porphyrin focal points enables concentrating light at the latter. Control over excitonic interactions within, for example, the electron-donating porphyrin dimers was realized by complexation of bidentate ligands to set up panchromatic absorption that extends all the way into the near-infrared range. The bidentate binding motif was then exploited to create a supramolecular electron donor-acceptor assembly based on a HBC-ethynyl-porphyrin dimer and an electron accepting bis(aminoalkyl)-substituted fullerene. Of great relevance is the fact that charge separation from the photoexcited HBC-ethynyl-porphyrin dimer to the bis(aminoalkyl)-substituted fullerene is activated not only upon photoexciting the HBCs in the UV as well as the (metallo)porphyrins in the visible but also in the NIR. Implicit is the synergetic interplay of energy and charge transfer in a photosynthetic mimicking manner. The dimer and bis-HBC-ethynyl-porphyrin monomers, which serve as references, were probed by means of steady-state as well as time-resolved optical spectroscopies, including global target analyses of the time-resolved transient absorption data.
CRIS-Team Scopus Importer:2020-07-31

Panchromatic PAH-Porphyrin Hybrids with a Step-Wise Increasing π-System - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (ChemistryOpen, 2025)
The rational synthesis of three β-meso-fused porphyrins with a step-wise increasing π-system size is presented. The synthetic route, which introduces a five-membered ring between the macrocycle and an aromatic fragment, is modular in its nature and proceeds straightforwardly. The well-soluble conjugates have intriguing optical properties, namely bathochromically shifted and flattened absorption curves. Density functional theory (DFT) calculations provide insights into the electronic structure and transitions, unveiling small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-extension

Photoinduced energy and electron transfer processes in hexapyropheophorbide a-fullerene [C60] molecular systems - Regehly, Martin; Ermilov, Eugeny; Helmreich, Matthias; Hirsch, Andreas; Jux, Norbert; Röder, Beate (Journal of Physical Chemistry B, 2007)
The photophysical properties of the novel hexapyropheophorbide a (P6), and hexakis (pyropheophorbide a)-C6o (FP6) were studied and compared with those of hexakis (pyropheophorbide a)-fullerene [5:1] hexaadduct (FHP6). It was found that after light absorption the pyropheophorbide a molecules in all three compounds undergo very efficient energy transfer as well as partly excitonic interactions. The last process results in the formation of energy traps, which could be resolved experimentally. For P6, due to shorter distances between neighboring dye molecules, stronger interactions between pyropheophorbide a units than for FHP6 were observed. As a consequence, the excitation energy is delivered rapidly to traps formed by stacked pyropheophorbide a molecules resulting in the reduction of fluorescence, intersystem crossing, and singlet oxygen quantum yields compared to the values of FHP6. For FP6 the reduction of these values is much stronger due to an additional fast and efficient deactivation process, namely photoinduced electron transfer from pyropheophorbide a to the fullerene moiety. Consequently, FP6 can be considered as a combination of a light-harvesting system consisting of several separate pyropheophorbide a molecules and a charge-separating center. © 2007 American Chemical Society.

Photophysical characterization of a ruthenium-based tetrameric pentacene complex - Hou, Yuxuan; Papadopoulos, Ilias; Ferguson, Michael J.; Jux, Norbert; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2023)
The synthesis of a ruthenium(II) tetramer (Ru(Lpc)4Cl2) bearing pyridyl pentacene-based ligands and its corresponding model complex lacking pentacene moieties (Ru(Lref)4Cl2) is presented. The formation of these tetramers is corroborated by 1H, 13C NMR, and IR spectroscopies, as well as X-ray crystallography and mass spectrometry. Photophysical properties of the tetramers are probed by steady-state and time-resolved transient absorption spectroscopy. Steady-state absorption and fluorescence assays suggest weak ground-state interactions between the pentacene moieties of Ru(Lpc)4Cl2 and sizeable metal-to-ligand interactions, which are ruthenium-to-pentacene based. Time-resolved transient absorption measurements reveal an ultrafast singlet-to-triplet transition that occurs on the femtosecond timescale and that yields vibrationally hot and solvent unrelaxed triplet excited states. After relaxation, these triplet excited states deactivate back to the ground state in less than 3 μs. These observations lead us to conclude that intersystem crossing outperforms photophysical processes such as singlet fission.
CRIS-Team Scopus Importer:2023-05-26
Keywords: excited state dynamics; intersystem crossing; pentacene; ruthenium complex; singlet fission

Photophysical properties of fullerene-dendron-pyropheophorbide supramolecules - Ermilov, Eugeny; Al-Omari, S.; Helmreich, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Chemical Physics, 2004)
Two novel monofullerene-bis(pyropheophorbide a) complexes were synthesized and their photophysical properties were studied by using both steady-state and time-resolved techniques. It was revealed that in the pyropheophorbide a (pyroPheo)-C molecular system (FP1) strong quenching of the first excited singlet state of the pyroPheo and, as result, dramatically decreasing of photosensitized singlet oxygen generation occurs by efficient photoinduced electron transfer to the fullerene molecule with a rate constant of 2.5×10 s. In contrast, the fullerene hexaadduct-bis(pyroPheo) system (FHP1), which possesses five diethyl malonate addends in the remaining octahedral positions, shows a high singlet oxygen quantum yield which is due to the reduced fullerene chromophore which is not a good electron acceptor anymore. © 2004 Elsevier B.V. All rights reserved.

Polymorphism of porphyrin molecules on Ag(111) and how to weave a rigid monolayer - Buchner, Florian; Comanici, Karmen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2007)
The molecular arrangement and the internal conformation of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (Co(II)-TTBPP) on Ag(111) was studied by scanning tunneling microscopy (STM) under ultrahigh vacuum (UHV) conditions. Interestingly, four different molecular arrangements were found using different routes to prepare the porphyrin films. After the preparation of a film with a coverage slightly below one monolayer by thermal sublimation, three clearly distinguishable molecular arrangements could be observed. Alternatively, a monolayer was prepared by deposition of a multilayer followed by subsequent annealing to desorb the excess multilayer molecules. Thereby, an additional, very rigid herringbone structure formed via a thermally activated process, covering most of the surface. The four ordered phases go along with different conformations of the individual molecules. On the basis of STM images with submolecular resolution, models for the lateral arrangements of the different polymorphs including the internal conformation of the individual molecules are proposed. Thereby, as an extension to previous works, the rotation of the upper tert-butyl groups of Co-TTBPP was taken into account. The derived molecular arrangements in combination with the intramolecular conformations give insight into the intermolecular interactions within and the nature of the different molecular phases. © 2007 American Chemical Society.

Porphyrin-Hexaphenylbenzene Conjugates via Mixed Cyclotrimerization Reactions - Martin, Max; Dill, Maximilian; Langer, Jens; Jux, Norbert (Journal of Organic Chemistry, 2019)
Mixed cyclotrimerization reactions of diarylacetylenes (tolans) were applied to generate a library of multiple porphyrin-hexaphenylbenzene (HPB) architectures. Successful reactions, which could be influenced by the ratio of tolan starting materials, were conducted using dicobaltoctacarbonyl as a catalyst. Separation of the reaction products was performed by chromatographic and crystallization techniques. The physical properties were investigated with respect to the number of porphyrins per HPB and their substitution pattern.
CRIS-Team WoS Importer:2019-02-21

Porphyrin-rylene-diimide-hexabenzocoronene triads - Martin, Max; Dusold, Carolin; Hirsch, Andreas; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2020)
Hexa-peri-hexabenzocoronenes (HBCs), substituted by two different chromophores in an ortho arrangement, were synthesized for the first time and investigated towards their photophysical properties. Rylene-diimide dyes, in particular naphthalene-diimides (NDIs) and perylene-diimides (PDIs), were attached to the HBC as the first, and porphyrins as the second chromophore. Therefore, porphyrin-NDI-HPB as well as porphyrin-PDI-HPB precursors were accessed and converted into the respective HBC derivatives applying oxidative Scholl conditions. UV-vis absorption and fluorescence emission spectroscopy showed interesting photophysical behavior such as energy transfer processes. Particularly, the porphyrin-PDI-HBC displays pronounced absorption features between 330-650 nm, which cover a wide range of the visible spectrum.
CRIS-Team Scopus Importer:2019-08-23
Keywords: hexabenzocoronene; nanographene; naphthalene; perylene; porphyrin; rylene-diimide

Positive Charge on Porphyrin Ligand and Nature of Metal Center Define Basic Physicochemical Properties of Cationic Manganese and Iron Porphyrins in Aqueous Solution - Franke, Alicja; Scheitler, Andreas; Kenkel, Isabell; Lippert, Rainer; Zahl, Achim; Balbinot, Domenico; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2019)
Recently, comprehensive studies on positively charged manganese porphyrins show that these compounds, known for their superoxide dismutase (SOD) mimetic ability, can be equally reactive toward a broad array of other redox active molecules of biological relevance present in a cellular milieu. In this context, the examination of some fundamental aspects of physicochemical behavior of metalloporphyrins behind their rich aqueous chemistry is believed to provide a valuable basis for the understanding of newly observed biological effects of these compounds in vivo and throw more light on a potential use of common SOD porphyrin mimetics for other redox active cellular targets in order to earn desirable therapeutic effects. Herein, we present versatile characteristics of highly positively charged Mn(P) and Fe(P) porphyrins (with up to +9 and +8 overall charge, respectively) with regard to their acid-base equilibria, metal coordination sphere, water-exchange dynamics, redox properties, and substitution behavior toward selected ligands. For the purpose of these comparative studies, we synthesized for the first time a 9-fold cationic manganese(III) porphyrin. The findings reported in this study enabled highlighting the most important similarities and differences characterizing the aqueous chemistry of positively charged manganese and iron porphyrins and, therefore, outlining the potential factors which can affect the intimate underlying mechanism behind the redox cycling of these metalloporphyrins.
CRIS-Team Scopus Importer:2019-08-30

Principle and mechanism of direct porphyrin metalation: Joint experimental and theoretical investigation - Shubina, Tatyana; Marbach, Hubertus; Flechtner, Ken; Kretschmann, Andreas; Jux, Norbert; Buchner, Florian; Steinrück, Hans-Peter; Clark, Timothy; Gottfried, Michael (Journal of the American Chemical Society, 2007)
The direct metalation of tetraphenylporphyrin with bare metal atoms (Co and Zn) was studied with X-ray photoelectron spectroscopy, scanning tunneling microscopy, and temperature-programmed reaction measurements on ordered monolayer films of the molecules adsorbed on a Ag(111) surface. The mechanism of this novel type of surface reaction was investigated using density functional theory (DFT) calculations for the related gas-phase reactions of the unsubstituted porphyrin with the metals Fe, Co, Ni, Cu, and Zn. The reaction starts with the formation of an initial complex, in which the metal atom is coordinated by the intact unreduced porphyrin. This complex resembles the sitting-atop complex proposed for porphyrin metalation with metal ions in solution. In two subsequent steps, the pyrrolic hydrogen atoms are transferred to the metal atom, forming H , which is eventually released. The activation barriers of the H-transfer steps vary for the different metal atoms. DFT calculations suggest that metalations with Fe, Co, and Ni show two-state reactivity, while those with Cu and Zn proceed on a single potential energy surface. For metalation with Zn, we calculated a barrier of the first hydrogen transfer step of 32.6 kcal mol , in good agreement with the overall experimental activation energy of 31 kcal mol . © 2007 American Chemical Society.

Probing Charge Management across the π-Systems of Nanographenes in Regioisomeric Electron Donor-Acceptor Architectures - Hölzel, Helen; Haines, Philipp; Kaur, Ramandeep; Lungerich, Dominik; Jux, Norbert; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Inspired by light-induced processes in nature to mimic the primary events in the photosynthetic reaction centers, novel functional materials combine electron donors and acceptors, i.e., (metallo)porphyrins (ZnP) and fullerenes (C60), respectively, with emerging materials, i.e., nanographenes. We utilized hexa-peri-hexabenzocoronene (HBC) due to its versatility regarding functionalization and physicochemical properties, to construct three regioisomeric ZnP-HBC-C60 conjugates, which foster geometrical diversity by arranging ZnP and C60 in ortho-, meta-, and para-positions to each other. The corresponding hexaarylbenzene (HAB) motifs, with an interrupted π-system, were also prepared. Transient absorption measurements disclosed the fast population of charge transfer as well as singlet and triplet charge-separated states. With the help of density functional theory (DFT) calculations, we further conceive the communication across the HBCs and HABs. This work reveals the impact of both the geometrical arrangement with respect to through-space versus through-bond interactions and the structural rigidity/flexibility on the charge management across the different π-systems.
CRIS-Team Scopus Importer:2022-06-10

Pyridinic Nanographenes by Novel Precursor Design - Reger, David; Schöll, Kilian; Hampel, Frank; Maid, Harald; Jux, Norbert (Chemistry - A European Journal, 2021)
In this work we present the solution-synthesis of pyridine analogues to hexa-peri-hexabenzocoronene (HBC)-which might be called superpyridines-via a novel precursor design. The key step in our strategy was the pre-formation of the C-C bonds between the 3/3' positions of the pyridine and the adjacent phenyl rings-bonds that are otherwise unreactive and difficult to close under Scholl-conditions. Apart from the synthesis of the parent compound we show that classical pyridine chemistry, namely oxidation, N-alkylation and metal-coordination is applicable to the pi-extended analogue. Furthermore, we present basic physical chemical characterizations of the newly synthesized molecules. With this novel synthetic strategy, we hope to unlock the pyridine chemistry of nanographenes.
CRIS-Team WoS Importer:2021-01-29

Reactions of Superoxide with Iron Porphyrins in the Bulk and the Near-Surface Region of Ionic Liquids - Dees, Anne; Jux, Norbert; Tröppner, Oliver; Dürr, Katharina L.; Lippert, Rainer; Schmid, Martin; Kuestner, Bernd; Schluecker, Sebastian; Steinrück, Hans-Peter; Gottfried, J. Michael; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2015)
The redox reaction of superoxide (KO2) with highly charged iron porphyrins (Fe(P4+), Fe(P8+), and Fe(P8-)) has been investigated in the ionic liquids (IL) [EMIM] [Tf2N] (1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide) and [EMIM] [B(CN)(4)] (1-ethyl-3-methylimidazolium tetracyanoborate) by using time-resolved UV/vis stopped-flow, electrochemistry, cryospray mass spectrometry, EPR, and XPS measurements. Stable KO2 solutions in [EMIM] [Tf2N] can be prepared up to a IS mM concentration and are characterized by a signal in EPR spectrum at g = 2.0039 and by the 1215 cm(-1) stretching vibration in the resonance Raman spectrum While the negatively charged iron porphyrin Fe(P8-) does not react with superoxide in IL, Fe(P4+) and Fe(P8+) do react in a two-step process (first a reduction of the Fe(III) to the Fe(II) form, followed by the binding of superoxide to Fe(II)). In the reaction with KO2, Fe(P4+) and Fe(P8+) show similar rate constants (e.g., in the case of Fe(P4+): k(1) = 18.6 +/- 0.5 M-1 s(-1) for the first reaction step, and k(2) = 2.8 +/- 0.1 M-1 s(-1) for the second reaction step). Notably, these rate constants are four to five orders of magnitude lower in [EMIM] [Tf2N] than in conventional solvents such as DMSO. The influence of the ionic liquid is also apparent during electrochemical experiments, where the redox potentials for the corresponding Fe(III)/Fe(II) couples are much more negative in [EMIM] [Tf2N] than in DMSO. This modified redox and kinetic behavior of the positively charged iron porphyrins results from their interactions with the anions of the ionic liquid, while the nucleophilicity of the superoxide is reduced by its interactions with the cations of the ionic liquid. A negligible vapor pressure of [EMIM][B(CN)(4)] and a sufficient enrichment of Fe(P8+) in a close proximity to the surface enabled XPS measurements as a case study for monitoring direct changes in the electronic structure of the metal centers during redox processes in solution and at liquid/solid interfaces.

Reverse Spin-Crossover and High-Pressure Kinetics of the Heme Iron Center Relevant for the Operation of Heme Proteins under Deep-Sea Conditions - Tröppner, Oliver; Lippert, Rainer; Shubina, Tatyana; Zahl, Achim; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Angewandte Chemie International Edition, 2014)
By design of a heme model complex with a binding pocket of appropriate size and flexibility, and by elucidating its kinetics and thermodynamics under elevated pressures, some of the pressure effects are demonstrated relevant for operation of heme-proteins under deep-sea conditions. Opposite from classical paradigms of the spin-crossover and reaction kinetics, a pressure increase can cause deceleration of the small-molecule binding to the vacant coordination site of the heme-center in a confined space and stabilize a high-spin state of its Fe center. This reverse high-pressure behavior can be achieved only if the volume changes related to the conformational transformation of the cavity can offset the volume changes caused by the substrate binding. It is speculated that based on these criteria nature could make a selection of structures of heme pockets that assist in reducing metabolic activity and enzymatic side reactions under extreme pressure conditions.
Keywords: confined space; heme proteins; high pressure; small-molecule binding; spin crossover

Reversible thermally induced phase transition in ordered domains of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin on Cu(111) - Steinrück, Hans-Peter; Stark, Michael Werner; Ditze, Stefanie; Thomann, Michael; Lungerich, Dominik; Jux, Norbert; Marbach, Hubertus (Surface Science, 2016)
We investigated the adsorption behavior of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (CoTTBPP) on Cu(111) by scanning tunneling microscopy (STM). At room temperature (RT), the coverage dependent adsorption behavior follows an expected scheme: at low coverage step decoration is found, which evolves into supramolecular domains with a hexagonal order at higher coverage. Interestingly, upon cooling the sample to 180 K the occurrence of a clearly distinguishable coexisting herringbone phase is observed. Upon heating to RT again, the herringbone phase vanishes. Thus a temperature dependent, fully reversible phase transition was observed. High resolution STM micrographs allow for the determination of the intramolecular conformations which are different for the two supramolecular arrangements. In addition, we studied the bias voltage dependent appearance of the molecule in STM and assigned a dominant contribution of the central Co at negative bias voltages close to the Fermi edge to the occupied d orbital. Interestingly, the herringbone phase, which dominates at 180 K, exhibits a significantly higher molecular density than the monomodal hexagonal arrangement at RT, which is in line with the "normal" behavior of freezing substances.
Keywords: Bias voltage dependence; Intramolecular conformation; Porphyrin; Reversible phase transition; Scanning tunneling microscopy; Self-assembly

Role of Specific Intermolecular Interactions for the Arrangement of Ni(II)-5, 10, 15, 20-Tetraphenyltetrabenzoporphyrin on Cu(111) - Lepper, Michael; Zhang, Liang; Stark, Michael Werner; Ditze, Stefanie; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2015)
We have studied the coverage-dependent adsorption behavior of Ni(II)-5,10,15,20-tetraphenyltetra-benzoporphyrin on Cu(111) by scanning tunneling microscopy (STM) at room temperature. At medium coverages, the molecules self-assemble into two-dimensional islands, due to mutual stabilization through intermolecular interactions. Altogether, three different supramolecular arrangements coexist at low-to-medium coverages. On the basis of high-resolution STM images and density functional theory calculations, models for the three arrangements and the corresponding intramolecular conformations of the individual molecules are proposed. The observed polymorphism is attributed to a complex interplay of specific T-type and pi-pi stacking interactions between the phenyl groups. For Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin, in which the aromatic periphery is modified by the attachment of tert-butyl groups, only one supramolecular arrangement on Cu(111) is found. This difference highlights the fact that the choice of peripheral ligands of the porphyrin derivatives plays an important role in the fabrication and tailoring of functional molecular architectures.

Screening Nanographene-Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces - Haines, Philipp; Kaur, Ramandeep; Martin, Max; Minameyer, Martin; Frühwald, Stefan; Bönisch, Simon; Lungerich, Dominik; Hampel, Frank; Görling, Andreas; Drewello, Thomas; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2021)
Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa-peri-hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investigations is to screen inter(porphyrin) communications across the HBC platform as a function of the substitution pattern and to optimize the intermolecular forces with fullerenes. To this end, the ground- and excited-state features are investigated in the absence of C60 and C70 by employing an arsenal of spectroscopic methods. Further insights into inter(porphyrin) communications come from time-dependent density-functional theory (TDDFT) calculations. In the presence of C60 and C70, X-ray crystallography, steady-state and time-resolved spectroscopy, and mass spectrometry corroborate exceptionally strong inter(porphyrin–fullerene) interactions in the solid, liquid, and gas phases. The experiments are backed-up with DFT calculations of the geometrically optimized and energetically stable complex configuration.
CRIS-Team Scopus Importer:2021-03-26
Keywords: charge separation; crystal structure; fullerene; hexabenzocoronene; porphyrin; transient absorption

Screening Supramolecular Interactions between Carbon Nanodots and Porphyrins - Cadranel, Alejandro; Strauß, Volker; Margraf, Johannes; Winterfeld, Kim; Vogl, Christoph; Dordevic, Luka; Arcudi, Francesca; Hölzel, Helen; Jux, Norbert; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
We present an in-depth investigation regarding the electron-accepting nature of pressure-synthesized carbon nanodots (pCNDs) in combination with porphyrins as excited-state electron donors. To this end, electrostatic attractions involving negative charges, which are present on the pCND surface, are essential to govern the hybrid assembly, on one hand, and charge separation, on the other hand.
CRIS-Team Scopus Importer:2022-04-14

Self-Assembled 2D-Coordination Kagome, Quadratic, and Close-Packed Hexagonal Lattices Formed from a Cyano-Functionalized Benzoporphyrin on Cu(111) - Adhikari, Rajan; Kuliga, Jan; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2021)
We investigated the adsorption of 2H-5,10,15,20-Tetracyanophenyl-Tetrabenzoporphyrin (2H-TCNPTBP) molecules on Cu(111) by scanning tunneling microscopy in ultrahigh vacuum at room temperature. Three types of network structures are observed to coexist on the surface. The first two, a porous Kagome lattice and a porous quadratic structure, are stabilized by cyano-Cu-cyano bonds with Cu adatoms; the third is a close-packed hexagonal network, with much weaker intermolecular H-bonds and dipole-dipole interactions of oppositely oriented cyano end groups. The coexistence of the three structures is attributed to very similar energetics. While the two metal-coordinated porous structures with identical molecular density are stabilized by the energy gain due to the network formation, the hexagonal network compensates the weaker intermolecular interactions by a factor of 2.3 higher molecular density; furthermore, kinetic stabilization might play a role. Our results show that cyano functionalization of benzoporphyrins gives rise to unusual two-dimensional self-Assembled lattice structures.
CRIS-Team Scopus Importer:2021-05-14

Self-assembly and coverage dependent thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin on Cu(111) - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2015)
A systematic scanning tunnelling microscopy investigation of the self-assembly and of thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin (Ni-TTBPBP) on Cu(111) is presented. At room temperature, Ni-TTBPBPs diffuse on the surface and self-assemble into ordered islands with well-defined registry to the substrate, with two different azimuthal orientations. The formation of the characteristic supramolecular structure is attributed to van der Waals interactions between the tert-butyl groups. Upon moderate heating, the intramolecular conformation changes irreversibly due to a dehydrogenative intramolecular aryl-aryl coupling reaction. This reaction is coverage dependent, with a lower rate at higher initial coverage; this behaviour is attributed to a stabilization of Ni-TTBPBP in the ordered islands at higher coverage.

Solution behavior of iron(iii) and iron(ii) porphyrins in DMSO and reaction with superoxide. Effect of neighboring positive charge on thermodynamics, kinetics and nature of iron-(su)peroxo product - Dürr, Katharina L.; Tröppner, Oliver; Olah, J.; Li, Jing; Zahl, Achim; Drewello, Thomas; Jux, Norbert; Harvey, Jeremy N.; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2012)

Steady-state and time-resolved studies on the photophysical properties of fullerene-pyropheophorbide a complexes in polar and nonpolar solvents - Ermilov, Eugeny; Al-Omari, S.; Helmreich, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Optics Communications, 2004)
A novel monofullerene-bis(pyropheophorbide a) dyad has been photophysically characterized by steady-state as well as time-resolved techniques. It was revealed that in this complex strong and fast quenching of the first excited singlet state of the pyropheophorbide a (pyroPheo) molecule occurs by efficient photoinduced electron transfer to the fullerene moiety in both polar (DMF) and nonpolar (toluene) solvents. In DMF the energy of the charge-separated state is 0.94 eV and it undergoes directly transition to the ground state resulting in a very low value of photosensitized singlet oxygen generation. In contrast to the situation in a polar solvent, in toluene the charge-separated state lies above the exited triplet state of pyroPheo as well as that of C. It has been shown that in a nonpolar solvent a sufficient amount of singlet oxygen was generated by energy transfer from the excited triplet state of pyroPheo which has been populated via relaxation of the charge-separated state. © 2004 Elsevier B.V. All rights reserved.

Structure and Conformation of Individual Molecules upon Adsorption of a Mixture of Benzoporphyrins on Ag(111), Cu(111), and Cu(110) Surfaces - Adhikari, Rajan; Brox, Jan; Massicot, Stephen; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (ChemPhysChem, 2023)
We investigated the adsorption behavior of a mixture of six 2H-tetrakis-(3, 5-di-tert-butylphenyl)(x)benzoporphyrins (2H-diTTBP(x)BPs, x=0, 1, 2-cis, 2-trans, 3, and 4) on Ag(111), Cu(111) and Cu(110) at room temperature by scanning tunneling microscopy (STM) under ultra-high vacuum conditions. On Ag(111), we observe an ordered two-dimensional square phase, which is stable up to 400 K. On Cu(111), the same square phase coexists with a stripe phase, which disappears at 400 K. In contrast, on Cu(110), 2H-diTTBP(x)BPs adsorb as immobile isolated molecules or dispersed short chains along the [1 (Formula presented.) 0] substrate direction, which remain intact up to 450 K. The stabilization of the 2D supramolecular structures on Ag(111) and Cu(111), and of the 1D short chains on Cu(110) is attributed to van der Waals interactions between the tert-butyl and phenyl groups of neighboring molecules. From high-resolution STM, we can assign all six 2H-diTTBP(x)BPs within the ordered structures. Moreover, we deduce a crown shape quadratic conformation on Ag(111) and Cu(111), an additional saddle-shape on Cu(111), and an inverted structure and a quadratic appearance on Cu(110). The different conformations are attributed to the different degree of interaction of the iminic nitrogen atoms of the isoindole and pyrrole groups with the substrate atoms.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 2H-diTTBP(x)BPs; benzoporphyrin; isoindole groups; scanning tunneling microscopy; self-assembly

Studies on an iron(iii)-peroxo porphyrin. Iron(iii)-peroxo or iron(ii)-superoxo? - Dürr, Katharina L.; Olah, Julianna; Davydov, Roman; Kleimann, Michael; Li, Jing; Lang, Nina; Puchta, Ralph; Hübner, Eike; Drewello, Thomas; Harvey, Jeremy N.; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2010)
We demonstrate that a one electron reduced product of the heme iron dioxygen adduct exists in solution not only as the commonly accepted iron(iii)-peroxo species, but coexists with its isomeric iron(ii)-superoxo form. This unusual reduced metal-superoxide adduct [M(ii)-O] is recently reported as a reactive intermediate in the case of non-heme extradiol dioxygenases and could also be generated by cryoreduction of a heme Fe-O adduct. The existence of iron(ii)-superoxo species in solution is consistent with IR, EPR, mass and Mössbauer spectra. The equilibrium between heme iron(iii)-peroxo and iron(ii)-superoxo forms is supported by density functional theory and explains our previous finding that upon release of coordinated (su)peroxide a corresponding iron(ii) complex remains. These results shed new light on the nature of heme iron(iii)-peroxo species that are key intermediates in the metalloenzyme-catalyzed dioxygen and hydrogen peroxide activation. © 2010 The Royal Society of Chemistry.

Superhelicenes in the gas phase: experimental and computational evidence of stable radical cation dimers - Kinzelmann, Marina; Reger, David; Warmbrunn, Vera; Lungerich, Dominik; Jux, Norbert; Drewello, Thomas (Chemical Communications, 2023)
Electrospray-ionization mass spectrometry (ESI-MS) readily produces stable radical cation pi-dimers of the superhelicenes. Energy-resolved collision experiments reveal the dissociation of the dicationic dimer into two singly charged superhelicenes. DFT calculations indicate that open-shell dications composed of two radical cations are thermochemically more attractive than the closed-shell dimer formed by a doubly charged and a neutral superhelicene.
CRIS-Team WoS Importer:2023-05-12

Supramolecular complexation of C60 and C70 by helical nanographene incorporating N-heterotriangulene and hexabenzocoronene subunits - Kinzelmann, Marina; Fröhlich, Nina; Gnannt, Frederik; Borstelmann, Jan; Frühwald, Stefan; Oleszak, Christoph; Jux, Norbert; Görling, Andreas; Kivala, Milan; Drewello, Thomas (RSC Advances, 2025)
Supramolecular host–guest complexes are studied in the gas-phase evaluating a new host molecule for fullerenes (C60 and C70). The new host molecule is a double N-heterotriangulene-[5]helicene (NTH), consisting of two N-heterotriangulene (N-HTA) blades embedded into a hexabenzocoronene-like backbone with helically curved topology. Host–guest complexes of [1:1]+c/2+, [1:2]+c/2+, [2:1]2+ and [2:3]2+ stoichiometry and charge state are formed by electrospray ionization-mass spectrometry (ESI-MS). Ion formation occurs through electrochemical oxidation of the N-HTA moieties. Energy-resolved collision-induced dissociation (ER-CID) experiments reveal the noncovalent binding of the fullerenes to the NTH molecule and provide an order of stability for the complexes. Density-functional theory (DFT) calculations establish the lowest energy geometries of the complexes.
CRIS-Team Scopus Importer:2025-02-14

Supramolecular order and structural dynamics: A STM study of 2H-tetraphenylporphycene on Cu(111) - Stark, Michael Werner; Träg, Johannes; Ditze, Stefanie; Brenner, Wolfgang; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Chemical Physics, 2015)
The adsorption of 2H-tetraphenylporphycene (2HTPPc) on Cu(111) was investigated by scanning tunneling microscopy (STM). At medium coverages, supramolecular ordered islands are observed. The individual 2HTPPc molecules appear as two pairs of intense protrusions which are separated by an elongated depression. In the islands, the molecules are organized in rows oriented along one of the close packed Cu(111) substrate rows; the structure is stabilized by T-type interactions of the phenyl substituents of neighboring molecules. Two types of rows are observed, namely, highly ordered rows in which all molecules exhibit the same orientation, and less ordered rows in which the molecules exhibit two perpendicular orientations. Altogether, three different azimuthal orientations of 2HTPPc are observed within one domain, all of them rotated by 15° ± 1° relative to one closed packed Cu direction. The highly ordered rows are always separated by either one or two less ordered rows, with the latter structure being the thermodynamically more stable one. The situation in the islands is highly dynamic, such that molecules in the less ordered rows occasionally change orientation, also complete highly ordered rows can move. The supramolecular order and structural dynamics are discussed on the basis of the specific molecule-substrate and molecule-molecule interactions.

Synthesis and characterization of novel "clicked" dimers of unsymmetrically substituted tetraphenylporphyrins - Malig, Jenny; Strauß, Volker; Grönninger, Philipp; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2011)
Herein, we present a novel and facile approach to porphyrin tweezer scaffolds through copper catalyzed azide alkyne cycloaddition (CuAAC). To this end, asymmetric structures arise that are highly versatile precursors for the molecular design of multi-functional porphyrin systems. The synthesis and characterization by means of photophysical and electrochemical methods and first results on the formation of dye-sensitized solar cells (DSSC) are described. © 2011 World Scientific Publishing Company.

Synthesis and first X-ray structure of a hexa-peri-hexabenzocoronene-fullerene-dyad: a model for an inter-carbon-allotrope hybrid. - Kratzer, Andreas; Englert, Jan; Lungerich, Dominik; Heinemann, Frank Wilhelm; Jux, Norbert; Hirsch, Andreas (Faraday Discussions, 2014)
The synthesis of a new hexa-peri-hexabenzocoronene (HBC)-fullerene dyad was accomplished involving a covalent linkage between both the planar and the spherical conjugated π-system of the two chromophores. We also present the first X-ray single crystal structure of a HBC-fullerene conjugate. A very short HBC-fullerene distance of 3.2 Å is observed. For the synthesis of this molecule, a new versatile applicable template, namely, a mono-functionalized hexa-peri-hexabenzocoronene was attached to a fullerene. Absorption and fluorescence spectroscopy, as well as quantum yield measurements of , indicated close electronic communication between the two subunits, which is promising for possible applications in molecular electronics.

Synthesis and in vitro testing of a pyropheophorbide-a-fullerene hexakis adduct immunoconjugate for photodynamic therapy - Rancan, Fiorenza; Helmreich, Matthias; Mölich, Andreas; Ermilov, Eugeny; Jux, Norbert; Röder, Beate; Hirsch, Andreas; Böhm, Fritz (Bioconjugate Chemistry, 2007)
The employment of carriers to enhance drug selectivity is one of the strategies to increase the efficacy and reduce the side effects of antitumor therapy. The concept of a modular carrier system (MCS) was developed to construct a complex drug having a high efficacy and selectivity. An MCS employs diverse units or modules: beside the therapeutic unit, an addressing unit (e.g., an antibody) serves to direct the drug to its target, and a multiplying unit has the role of increasing the number of biological active moieties the system can carry. In this paper, we report on the synthesis of a modular carrier system in which the role of multiplying unit is given to a [5:1]-fullerene hexakis adduct. This fullerene hexaadduct has five malonate spacers which can bind two therapeutic units (the photosensitizer pyropheophorbide-a) each, for a total of ten, and a longer malonate spacer which serves for the conjugation to the addressing unit, the monoclonal antibody rituximab. Confocal microscopy studies using Epstein-Barr virus-transformed B-lymphocytes and Jurkat cells showed that the antibody conjugate conserves the affinity for its receptor (CD20) and its selectivity toward CD20 positive B-lymphocytes. On the contrary, the antibody-free complex did not show any bounding or intracellular uptake. © 2007 American Chemical Society.

Synthesis and Photophysical Properties of Hexabenzocoronene-Tetrabenzoporphyrin Architectures - Ruppel, Michael; Gazetas, Lampros-Pascal; Lungerich, Dominik; Jux, Norbert (European Journal of Organic Chemistry, 2020)
Porphyrin-based architectures have emerged as excellent candidates for artificial light-harvesting antennae. Although tetrabenzoporphyrins (TBPs), the π-extended “bigger brothers” of porphyrins, benefit from increased absorptivity in the near-infrared (NIR), their utilization in light-harvesting systems is still in its infancy. Within this work, we prepared two donor-acceptor hetero dyads consisting of hexa-peri-hexabenzocoronenes (HBCs) to harvest high energetic near-UV light, and a TBP core, which serves as visible to NIR light antenna and as subsequent energy sink of the conjugate. The HBCs are either attached to the meso-position or via a maleimide-bridge on the periphery of the macrocycle. Upon excitation of the HBC moieties, both dyads exhibit an efficient energy transfer to the TBP core. Furthermore, the TBP-HBC dyads show superior light-harvesting properties compared to the respective HBC-porphyrin reference and the naturally occurring chlorophylls a/b.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Coronenes; Donor-acceptor systems; Excited energy transfer; Porphyrins

Synthesis and physico-chemical properties of porphycenes - Brenner, Wolfgang; Malig, Jenny; Oelsner, Christian; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2012)
A new and improved synthesis for porphycenes is presented. In particular, treating pyrroles with iodine monochloride results in quantitative yields and easier work up. This key step was employed for the synthesis of different 2,7,12,17-substituted porphycenes (TPrPc, TPPc, TtBPPc). The synthetic part of this project is followed by a global analysis of the physico-chemical properties of three exemplary porphycenes, including absorption, emission, and electrochemistry. In-situ UV-vis/nIR spectroelectrochemistry was used to determine the spectral signatures of the radical anion and cation species. Temperature-dependent fluorescence lifetimes were determined under air as well as under inert atmosphere. © 2012 World Scientific Publishing Company.

Synthesis of novel pyropheophorbide a-fullerene conjugates - Helmreich, Matthias; Hirsch, Andreas; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2005)
Two pyropheophorbide a units were attached via a malonate addition reaction to the [60]fullerene core to give a trichromophoric system. Also, in a different approach two pyropheophorbide a moieties were coupled to a hexasubstituted [60]fullerene diol. The monoadduct was very light and oxygen sensitive whereas the corresponding hexaadduct showed a much higher stability. Copyright © 2005 Society of Porphyrins & Phthalocyanines.

Testing electron transfer within molecular associates built around anionic C60 and C70 dendrofullerenes and a cationic zinc porphyrin - Sarova, Ginka; Hartnagel, Uwe; Balbinot, Domenico; Sali, Sevda; Jux, Norbert; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2008)
Mono- and bis-functionalized C and C fullerene derivatives (DF, 1-10) that carry one or two oligoanionic dendritic termini in their malonate addends and an oligocationic octapyridinium zinc porphyrin salt (ZnP) were found to self-assemble in buffered aqueous solution to yield a novel series of 1:1 and/or 1:2 electron transfer hybrid associates. Remarkably high association constants-typically on the order of 10 M - were derived that corroborate stable complex formations. A combination of electrostatic and charge-transfer interactions that are operative between the electron-accepting DF and the electron-donating ZnP is considered to contribute to the uniquely high complex stability. First insight into intracomplex excited state interactions came from steady-state and time-resolved fluorescence quenching experiments that were performed with the molecular ZnP/DF hybrid as_sociates. Excited state quenching processes are, for example, evident in form of a bi-exponential fluorescence decay of ZnP - corresponding to a distribution of associated and non-associated ZnP. Unambiguous evidence for an intracomplex electron transfer quenching, namely, formation of ZnP/C and ZnP/C radical ion pairs, was gathered in time-resolved transient absorption measurements. Lifetimes of these radical ion-pairs range from nanoseconds to a few microseconds. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

The dissociation behaviour of a singly and doubly charged (cationised) aza-crown ether/metalloporphyrin-conjugate: Metal-induced reactivity and Coulomb explosions Dedication: In memory of Prof. Detlef Schröder. - Li, Jing; Dürr, Katharina L.; von Gernler, Marc; Jux, Norbert; Ivanovic-Burmazovic, Ivana; Drewello, Thomas (International Journal of Mass Spectrometry, 2013)
Fe(III) and Mn(III) complexes of an aza-crown ether/porphyrin conjugate, 5-N-(4-aza-18-crown-6)methyl-5,10,15 ,20-tetra-tert-butyl-5-methyl-5,10,15,20- tetraphenylporphyrin, with Cl and Br as respective counter ions, are studied by electrospray ionisation (ESI)-mass spectrometry (MS). Fragmentation pathways are established by MS and MS collision-induced dissociation (CID) experiments performed with a quadrupole ion trap (QIT) and energy-dependent CID is studied with a quadrupole/time-of-flight (q-ToF) instrument. Singly charged ions are produced by selective protonation, sodiation or potassiation of the crown ether moiety, and dications possess one additional charge on the halide-released porphyrin metal cation. Singly charged parent ions undergo a two-step decay. Firstly, an "ion pair" is lost, composed of the cationic charge carrier of the crown ether and the anionic counter ion at the porphyrin. Secondly, the intact crown ether is released. The threshold of this process is dependent on the nature of the central porphyrin metal, with Fe(III) dramatically facilitating the reaction. The dications undergo two different Coulomb explosions: crown/porphyrin-fission and cation loss from the crown ether, the ratio of which is dependent on the affinity of the cation to the crown ether. © 2013 Elsevier B.V. All rights reserved.

Time-resolved imaging and analysis of the electron beam-induced formation of an open-cage metallo-azafullerene - Hölzel, Helen; Lee, Sol; Amsharov, Konstantin Yu; Jux, Norbert; Harano, Koji; Nakamura, Eiichi; Lungerich, Dominik (Nature Chemistry, 2023)
The visualization of single-molecule reactions provides crucial insights into chemical processes, and the ability to do so has grown with the advances in high-resolution transmission electron microscopy. There is currently a limited mechanistic understanding of chemical reactions under the electron beam. However, such reactions may enable synthetic methodologies that cannot be accessed by traditional organic chemistry methods. Here we demonstrate the synthetic use of the electron beam, by in-depth single-molecule, atomic-resolution, time-resolved transmission electron microscopy studies, in inducing the formation of a doubly holed fullerene-porphyrin cage structure from a well-defined benzoporphyrin precursor deposited on graphene. Through real-time imaging, we analyse the hybrid’s ability to host up to two Pb atoms, and subsequently probe the dynamics of the Pb–Pb binding motif in this exotic metallo-organic cage structure. Through simulation, we conclude that the secondary electrons, which accumulate in the periphery of the irradiated area, can also initiate chemical reactions. Consequently, designing advanced carbon nanostructures by electron-beam lithography will depend on the understanding and limitations of molecular radiation chemistry. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-09-29

Toward combining graphene and QDs: Assembling CdTe QDs to exfoliated graphite and nanographene in water - Katsukis, Georgios; Malig, Jenny; Schulz-Drost, Christian; Leubner, Susanne; Jux, Norbert; Guldi, Dirk Michael (Acs Nano, 2012)
Herein, we report for the first time on a full-fledged investigation of water-soluble CdTe quantum dots (QD) that are immobilized onto exfoliated graphite (EG) and/or nanographene (NG). Particular emphasis was placed on a top-down preparation of stable aqueous dispersions-starting from natural graphite rather than graphene oxide-while preserving the intrinsic properties of graphene. To this end, we circumvented the harsh conditions commonly employed for the pre-exfoliation (i.e., Hummers method). First, a hydrophobic- hydrophobic/π-π stacking motif was tested between EG and pyrene, to which QDs are covalently attached (QD-pyrene). Second, we employed the combination of hydrophobic-hydrophobic/π-π stacking and electrostatic interactions to build up hierarchical structures composed of NG, positively charged pyrene (pyrene ), and negatively charged QDs. The novel nanohybrids-QD- pyrene/EG and QD/pyrene /NG-were characterized with specific emphasis on electron-transfer chemistry. In fact, both assays provide kinetic and spectroscopic evidence that support electron transfer dynamics that vary, however, between EG and NG as a reflection of the different degree of graphite exfoliation. © 2012 American Chemical Society.

Toward multifunctional wet chemically functionalized graphene - Integration of oligomeric, molecular, and particulate building blocks that reveal photoactivity and redox activity - Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Accounts of Chemical Research, 2013)
Many technological applications indispensable in our daily lives rely on carbon. By altering the periodic binding motifs in networks of sp, sp, and sp-hybridized carbon atoms, researchers have produced a wide palette of carbon allotropes. Over the past two decades, the physicochemical properties of low-dimensional nanocarbons, including fullerenes (0D), carbon nanotubes (1D), and, most recently, graphene (2D), have been explored systematically.An entire area of research has focused on the chemistry of 1D nanocarbons, particularly single-wall carbon nanotubes. These structures exhibit unique electronic, mechanical, and optical properties. These properties are, however, only discernible for single-wall carbon nanotubes that are debundled, individualized, and stabilized, often in solution. Most prominently, they are small band gap, p-type semiconductors or metals with conductances that reach ballistic dimensions. These structures can have poor solubility in many media, and large bundles can originate from attractive interactions such as π-π stacking and London dispersion forces. Therefore, both covalent and noncovalent modifications of single-wall carbon nanotubes have emerged as powerful approaches to overcome some of these problems. Noncovalent functionalization is especially useful in improving the solubility without altering the electronic structure.We expect that many of the strategies that have recently been exploited and established in the context of 1D nanocarbons can be applied to the chemistry of 2D nanocarbons, especially graphene. Two-dimensional nanocarbons are currently attracting extensive attention due to their striking mechanical, optical, and electrical features. Nanocarbons that are a single atom thick are gapless semiconductors and exhibit electron mobilities reaching values of up to 15000 cm V s at room temperature. Researchers have made rapid progress in the covalent and/or noncovalent functionalization of graphene with photoactive and or redox active building blocks.In this Account, we summarize our work on the integration of photoactive and/or redox active building blocks, including oligomers, molecules, and particulates, onto graphenoid materials to yield multifunctional electron donor-acceptor conjugates and hybrids. Intriguingly, we produce graphene in the form of single-layer, bilayer, and multilayer graphene through the exfoliation of graphite by surface active agents. The exfoliation occurs through π-π, hydrophobic, van der Waals, electrostatic, and charge transfer interactions, and the surface active agents also serve as versatile anchor groups. We studied the electronic interactions in terms of photoactivity and/or redox activity in depth by steady-state and time-resolved spectroscopy. Finally, we present examples of proof-of-principle solar energy conversion devices. © 2012 American Chemical Society.

Towards tunable graphene/phthalocyanine-PPV hybrid systems - Malig, Jenny; Jux, Norbert; Kießling, Daniel; Cid, Juan-Jose; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2011)
Exfoliation of graphite was achieved using a zinc phthalocyanine oligomer that is also an electron donor. The resulting functionalized graphene material was investigated by Raman and electron spectroscopy and was trialed in a photoelectrochemical cell. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Towards understanding the competition of electron and energy transfer in “molecular” nanographenes on the example of hexa-peri-hexabenzocoronene - Beneventi, Giovanni Mariano; Krug, Marcel; Reger, David; Jux, Norbert; Guldi, Dirk Michael (Journal of Photochemistry and Photobiology C-Photochemistry Reviews, 2023)
Bottom-up strategies have allowed the synthesis of “molecular” nanographenes with full control over size, shape and functionality. In recent years, the progress on wet chemical approaches, oxidative cyclodehydrogenation amongst all, has been the foundation to the synthesis of an impressive number of soluble and well-defined molecular nanographenes. The level of control over nanographene syntheses has allowed a fine-tuning of the photophysical and electrochemical properties and, in turn, has a compelling potential in the field of material science. In this regard, understanding and harnessing the competition between electron transfer and energy transfer in nanographenic systems is of utmost importance. However, a comprehensive structure-property relationship remains still an open aspect. In the present review we describe a large variety of hexa-peri-hexabenzocoronene (HBC)-based nanographenes obtained through wet chemical strategies and linked – either covalently or non-covalently – to porphyrins, rylenes, fullerenes, etc. Particular attention was placed on the optical, electrochemical and excited-state properties.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Electron transfer; Energy transfer; Hexa-peri-hexabenzocoronene; Nanographene; Polycyclic aromatic hydrocarbons

Transient absorption spectroscopy of a monofullerene C60-bis- (pyropheophorbide a) molecular system in polar and nonpolar environments - Al-Omari, S.; Ermilov, Eugeny; Helmreich, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Applied Physics B-Lasers and Optics, 2004)
The population dynamics of the excited and ground states of the monofullerene-bis (pyropheophorbide a) complex (FP1) were studied in polar (DMF) and nonpolar (toluene) solvents using picosecond transient absorption techniques. A strong quenching of the fluorescence signal of FP1 was observed in both solvents, in comparison to the fluorescence of bis (pyropheophorbide a) (P2). This quenching is due to an intramolecular photoinduced electron transfer from the pyropheophorbide a (pyroPheo) moiety to the fullerene C monoadduct. In DMF the charge-separated (CS) state of FP1 has a lifetime of 0.32 ns and undergoes a direct transition to the ground state, resulting in a very low value of photosensitised singlet oxygen generation. In toluene, energy transfer from the first excited triplet state of pyroPheo, which has been populated via relaxation of the CS state, generates a considerable amount of singlet oxygen. The lifetime of the CS state in the nonpolar solvent was estimated to be 0.29 ns. It was also shown that in both DMF and toluene the first excited singlet state as well as the triplet state of the fullerene moiety in FP1 are not occupied.

Trap formation and energy transfer in the hexapyropheophorbide a - Fullerene C60 hexaadduct molecular system - Ermilov, Eugeny; Hackbarth, St.; Al-Omari, S.; Helmreich, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Optics Communications, 2005)
The photophysical properties of the novel hexapyropheophorbide a - fullerene hexaadduct (FHP6) compound were studied using both steady-state and time-resolved spectroscopic methods. It was found that neighboring pyropheophorbide a (pyroPheo) molecules covalently linked to one fullerene moiety due to the length and high flexibility of carbon chains could stack with each other. This structural property is the reason for the possibility of formation of two different types of energy traps, which could be resolved experimentally. One of them is formed via face-to-face stacking of two pyroPheo molecules with parallel to each other direction of the transition dipole moments. The second type of energy trap gives the dominant contribution to the fluorescence signal at registration wavelengths having the oblique geometry or orthogonal direction of the transition dipole moments of the interacting pyroPheo molecules. In any case the dipole-dipole resonant Förster energy transfer between pyroPheo molecules coupled to one fullerene moiety caused a very fast and efficient delivery of the excitation to a trap. As result the fluorescence as well as the singlet oxygen quantum yields of FHP6 were reduced three and two times, respectively, compared to those values of the reference bis pyropheophorbide a - fullerene hexaadduct (FHP1) compound. © 2005 Elsevier B.V. All rights reserved.

Unexpected Michael Additions on the Way to 2.3,8.9-Dibenzanthanthrenes with Interesting Structural Properties - Reus, Christian; Lechner, Marc; Schulze, Matthias; Lungerich, Dominik; Diner, Colin; Gruber, Marco; Stryker, Jeffrey M.; Hampel, Frank; Jux, Norbert; Tykwinski, Rik (Chemistry - A European Journal, 2016)
The synthesis and properties of a new polycyclic aromatic hydrocarbon containing eight annulated rings and based on the anthanthrene core is described. An unexpected, nucleophile-dependent Michael addition to a dibenzanthanthrene-1,7-dione is found, giving a product with three triisopropylsilylacetylene units and a remarkable solid-state structure (as determined by X-ray crystallography).
EAM Import::2019-03-12

Volume profile analysis for the reversible binding of superoxide to form iron(II)-superoxo/iron(III)-Peroxo porphyrin complexes - Dürr, Katharina L.; Jux, Norbert; Zahl, Achim; van Eldik, Rudi; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2010)
The one-electron reduced iron(II)-dioxygen adduct, Fe-O , is known to be an important intermediate in the catalytic cycle of heme (mono)oxygenases. The same type of species, considered as Fe-peroxo, can be formed in a direct reaction between a Fe center and superoxide. In a unique high-pressure study of the reaction between superoxide and the Fe complex of a crown ether porphyrin conjugate in dimethylsulfoxide (DMSO), the overall Fe -superoxide interaction mechanism could be visualized and the nature of all species that occur along the reaction coordinate could be clarified. The equilibrium between the low-spin and high-spin forms of the starting Fe complex was quantified, which turns out to be the actual activation step toward substitution and subsequent inner-sphere electron transfer reactions. The constructed reaction volume profile demonstrates that the reaction product consists of Fe-peroxo and Fe -superoxo species that exist in equilibrium, which can better account for the versatile reactivity of Fe-O adducts toward different substrates. © 2010 American Chemical Society.

Wet-chemically prepared porphyrin layers on rutile tio2(110) - Wechsler, Daniel; Carolina Fernandez, Cynthia; Köbl, Julia; Augustin, Lisa-Marie; Stumm, Corinna; Jux, Norbert; Steinrück, Hans-Peter; Williams, Federico Jose; Lytken, Ole (Molecules, 2021)
Porphyrins are large organic molecules that are interesting for different applications, such as photovoltaic cells, gas sensors, or in catalysis. For many of these applications, the interactions between adsorbed molecules and surfaces play a crucial role. Studies of porphyrins on surfaces typically fall into one of two groups: (1) evaporation onto well-defined single-crystal surfaces under well-controlled ultrahigh vacuum conditions or (2) more application-oriented wet chemical deposition onto less well-defined high surface area surfaces under ambient conditions. In this study, we will investigate the wet chemical deposition of 5-(monocarboxyphenyl)-10,15,20-triphenylporphyrin (MCTPP) on well-defined rutile TiO2 (110) single crystals under ambient conditions. Prior to deposition, the TiO2(110) crystals were also cleaned wet-chemically under ambient conditions, meaning none of the preparation steps were done in ultrahigh vacuum. However, after each preparation step, the surfaces were characterized in ultrahigh vacuum with X-ray photoelectron spectroscopy (XPS) and the result was compared with porphyrin layers prepared in ultrahigh vacuum (UHV) by evaporation. The differences of both preparations when exposed to zinc ion solutions will also be discussed.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Interfaces; Metalation; Oxide surfaces; Porphyrins; Wet chemical preparation

Zinc Porphyrin Metal-Center Exchange at the Solid-Liquid Interface - Franke, Matthias; Marchini, Florencia; Jux, Norbert; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Chemistry - A European Journal, 2016)
Demetalation of zinc 5,10,15,20-tetraphenylporphyrin (ZnTPP) under acidic conditions and ion exchange with Cu ions at neutral pH are both rapid reactions in the liquid medium. However, for ZnTPP monolayers adsorbed on a Au(111) surface exposed to aqueous solution, we find that, although ion exchange takes place rapidly as expected, demetalation does not occur, even at pH values as low as 0. Based on this, we conclude that metal center exchange on the surface does not proceed through a free-base porphyrin as an intermediate. Furthermore, once formed, CuTPP is stable on the surface and the reverse exchange from CuTPP to ZnTPP in the presence of Zn ions could not be achieved. The preference for copper is so strong that even an attempt to exchange adsorbed ZnTPP with Ni ions in the presence of traces of Cu yielded CuTPP rather than NiTPP.
Keywords: Ion exchange; Metalation; Porphyrins; Solid-liquid interfaces; Zinc

β-meso-Fused pyrene–porphyrin scaffolds with panchromatic absorption features - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (Organic & Biomolecular Chemistry, 2024)
The π-extension of porphyrins with pyrenes through the β-mesofusion of five-membered rings is demonstrated. Three architectures resulting from combining up to two porphyrins and pyrenes were obtained straightforwardly in good overall yields. Although significantly planarized, the molecules retain excellent solubility and processability. Spectroscopic characterization and density-functional theory calculations reveal intriguing absorption features.
CRIS-Team Scopus Importer:2025-02-04